Activation of human C-Fibers by Lysophosphatidic Acid - Düll, Miriam; Stengel, M.; Wurm, L.; Ries, V.; Kremer, Andreas; Namer, Barbara (2017)
EVALuna2:33350

Activation of human C-fibres by lysophosphatidic acid - Düll, Miriam; Stengel, M.; Wurm, L.; Ries, V.; Kremer, Andreas; Namer, Barbara (2017)
EVALuna2:33347

ADSCs and adipocytes are the main producers in the autotaxin-lysophosphatidic acid axis of breast cancer and healthy mammary tissue in vitro - Schmid, Rafael; Wolf, Katharina; Robering, Jan Willem; Strauss, Selina; Strissel, Pamela; Strick, Reiner; Rübner, Matthias; Fasching, Peter; Horch, Raymund E.; Kremer, Andreas; Boos, Anja; Weigand, Annika (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common malignancy in women affecting one out of eight females throughout their lives. Autotaxin (ATX) is upregulated in breast cancer which results in increased lysophosphatidic acid (LPA) formation within the tumor. This study's aim was to identify the role of different mammary cell populations within the ATX-LPA axis. METHODS: Epithelial-cell-adhesion-molecule-positive (EpCAM) and -negative cells from breast tumors, adipose-derived stem cells (ADSCs) of tumor-adjacent and tumor-distant mammary fat were isolated and compared to healthy ADSCs, mammary epithelial cells (HMECs), and mesenchymal cells (MES) of healthy mammary tissue (n = 4 each) and further to well-established breast (cancer) cell lines. RESULTS: mRNA expression analyses revealed that ADSCs and MES largely expressed LPA receptor 1 (LPAR1) while epithelial cells mainly expressed LPAR6. LPA 18:1 activated all the cell populations and cell lines by rise in cytosolic free calcium concentrations. MES and ADSCs expressed ATX whereas epithelial cells did not. ADSCs revealed the highest expression in ATX with a significant decline after adipogenic differentiation in healthy ADSCs, whereas ATX expression increased in ADSCs from tumor patients. Breast (cancer) cell lines did not express ATX. Transmigration of MES was stimulated by LPA whereas an inhibitory effect was observed in epithelial cells with no differences between tumors and healthy cells. Triple-negative breast cancer (TNBC) cell lines were also stimulated and the transmigration partly inhibited using the LPA receptor antagonist Ki16425. CONCLUSIONS: We here show that each mammary cell population plays a different role in the ATX-LPA axis with ADSCs and adipocytes being the main source of ATX in tumor patients in our experimental setting. Inhibitors of this axis may therefore present a valuable target for pharmacological therapies.
EVALuna2:35125

Advances in hepatitis C therapy: What is the current state - what come's next? - Zopf, Steffen; Kremer, Andreas; Neurath, Markus; Siebler, Jürgen (World Journal of Hepatology, 2016)
Chronic hepatitis C virus (HCV) infection affects 80-160 million people worldwide and is one of the leading causes of chronic liver disease. It is only a few years ago that standard treatment regimes were based on pegylated interferon alpha and ribavirin. However, treatment of HCV has undergone a revolutionary change in recent years. The admission of the nucleotide polymerase inhibitor Sofosbuvir enabled an interferon-free regimen with direct antiviral agents (DAA). Meanwhile seven DAAs are available and can be applied in several combinations for 8 to 24 wk depending on HCV genotype and patient characteristics such as cirrhosis and chronic renal failure. High rates of sustained virological response (SVR) rates can be achieved with these novel drugs. Even in difficult to treat populations such as patients with liver cirrhosis, HCV-human immunodeficiency virus co-infections, after liver transplantion, or with chronic kidney disease comparable high rates of SVR can be achieved. The anticipated 2(nd) generation DAAs are strikingly effective in patients so far classified as difficult to treat including decompensated liver cirrhosis or post-transplant patients. These 2(nd) generations DAAs will have higher resistance barriers, higher antiviral effects and a pan-genotypic spectrum. This review highlights the current state of the art of antiviral treatment in hepatitis C and gives an outlook for upcoming therapies.
EVALuna2:2078

Advances in pathogenesis and management of pruritus in cholestasis - Kremer, Andreas; Bolier, Ruth; Van Dijk, Remco; Elferink, Ronald P. J. Oude; Beuers, Ulrich (Digestive Diseases, 2014)
Chronic pruritus is a burdensome feature of numerous hepatobiliary disorders such as primary biliary cirrhosis, primary sclerosing cholangitis, cholangiocarcinoma, inherited forms of cholestasis and intrahepatic cholestasis of pregnancy. Bile salts, ?-opioids, serotonin, histamine and steroids have been controversially discussed in the pathogenesis of cholestatic pruritus. However, for these substances neither a correlation with itch severity nor a causative link has ever been established. Recent findings indicate that the potent neuronal activator lysophosphatidic acid and autotaxin, the enzyme forming lysophosphatidic acid, may play a key element in the pathogenesis of cholestatic pruritus. Serum activity of autotaxin correlated with itch intensity and response to antipruritic treatment in patients with cholestatic pruritus, but not other forms of pruritus. Autotaxin activity thereby represents the first biomarker for pruritus and had a positive predictive value of 70% in differentiating cholestatic pruritus from other forms of pruritus. Treatment options for patients with cholestatic pruritus include the anion exchange resin colestyramine, the PXR agonist rifampicin, the ?-opioid antagonist naltrexone, and the serotonin reuptake inhibitor sertraline. These drugs are recommended by evidence-based guidelines as a stepwise therapeutic approach. Patients unresponsive to these drugs should be referred to specialized centers to receive experimental approaches such as UVB phototherapy, albumin dialysis, plasmapheresis or nasobiliary drainage. This review discusses pruritogen candidates in cholestasis, gives novel insights into the neuronal signaling pathway of pruritus and summarizes evidence-based treatment options for patients suffering from pruritus in cholestasis.
EVALuna2:1863

A group of cationic amphiphilic drugs activates MRGPRX2 and induces scratching behavior in mice - Wolf, Katharina; Kühn, Helen; Boehm, Felicitas; Gebhardt, Lisa; Glaudo, Markus; Agelopoulos, Konstantin; Ständer, Sonja; Ectors, Philipp; Zahn, Dirk; Riedel, Yvonne K.; Thimm, Dominik; Müller, Christa E.; et al. (Journal of Allergy and Clinical Immunology, 2021)
Background: Mas gene–related G protein–coupled receptors (MRGPRs) are a G protein–coupled receptor family responsive to various exogenous and endogenous agonists, playing a fundamental role in pain and itch sensation. The primate-specific family member MRGPRX2 and its murine orthologue MRGPRB2 are expressed by mast cells mediating IgE-independent signaling and pseudoallergic drug reactions. Objectives: Our aim was to increase knowledge about the function and regulation of MRGPRX2/MRGPRB2, which is of major importance in prevention of drug hypersensitivity reactions and drug-induced pruritus. Methods: To identify novel MRGPR (ant)agonists, we screened a library of pharmacologically active compounds by utilizing a high-throughput calcium mobilization assay. The identified hit compounds were analyzed for their pseudoallergic and pruritogenic effects in mice and human. Results: We found a class of commonly used drugs activating MRGPRX2 that, to a large extent, consists of antidepressants, antiallergic drugs, and antipsychotics. Three-dimensional pharmacophore modeling revealed structural similarities of the identified agonists, classifying them as cationic amphiphilic drugs. Mast cell activation was investigated by using the 3 representatively selected antidepressants clomipramine, paroxetine, and desipramine. Indeed, we were able to show a concentration-dependent activation and MRGPRX2-dependent degranulation of the human mast cell line LAD2 (Laboratory of Allergic Diseases-2). Furthermore, clomipramine, paroxetine, and desipramine were able to induce degranulation of human skin and murine peritoneal mast cells. These substances elicited dose-dependent scratching behavior following intradermal injection into C57BL/6 mice but less so in MRGPRB2-mutant mice, as well as wheal-and-flare reactions following intradermal injections in humans. Conclusion: Our results contribute to the characterization of structure-activity relationships and functionality of MRGPRX2 ligands and facilitate prediction of adverse reactions such as drug-induced pruritus to prevent severe drug hypersensitivity reactions.
CRIS-Team Scopus Importer:2021-04-19
Keywords: (drug-induced) pruritus; Mas gene–related G protein–coupled receptors; mast cells; pseudoallergic drug reactions

A High-Calorie Diet Aggravates Mitochondrial Dysfunction and Triggers Severe Liver Damage in Wilson Disease Rats - Einer, Claudia; Leitzinger, Christin; Lichtmannegger, Josef; Eberhagen, Carola; Rieder, Tamara; Borchard, Sabine; Wimmer, Ralf; Denk, Gerald; Popper, Bastian; Neff, Frauke; Polishchuk, Elena; Polishchuk, Roman S.; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2019)
BACKGROUND & AIMS: In Wilson disease, ATP7B mutations impair copper excretion into bile. Hepatic copper accumulation may induce mild to moderate chronic liver damage or even acute liver failure. Etiologic factors for this heterogeneous phenotype remain enigmatic. Liver steatosis is a frequent finding in Wilson disease patients, suggesting that impaired copper homeostasis is linked with liver steatosis. Hepatic mitochondrial function is affected negatively both by copper overload and steatosis. Therefore, we addressed the question of whether a steatosis-promoting high-calorie diet aggravates liver damage in Wilson disease via amplified mitochondrial damage.
CRIS-Team WoS Importer:2019-05-03

Analysis of shear wave elastography and serum autotaxin as novel non-invasive markers of liver fibrosis in patients with autoimmune hepatitis - a prospective study - Janik, M. K.; Kruk, B.; Kostrzewa, K.; Raszeja-Wyszomirska, J.; Wolf, Katharina; Lammert, F.; Kremer, Andreas; Krawczyk, M.; Milkiewicz, P. (2017)
EVALuna2:33925

Antipruritic effect of bezafibrate and serum autotaxin measures in patients with primary biliary cholangitis - Kremer, Andreas; Le Cleac'H, Aline; Lemoinne, Sara; Wolf, Katharina; De Chaisemartin, Luc; Chollet-Martin, Sylvie; Humbert, Lydie; Rainteau, Dominique; Poupon, Raoul; Rousseau, Alexandra; Chazouilleres, Olivier; Corpechot, Christophe (Gut, 2019)
CRIS-Team WoS Importer:2019-11-29

A phase II, randomized, open-label, 52-week study of seladelpar in patients with primary biliary cholangitis - Bowlus, Christopher L.; Galambos, Michael R.; Aspinall, Richard J.; Hirschfield, Gideon M.; Jones, David E.J.; Dörffel, Yvonne; Gordon, Stuart C.; Harrison, Stephen A.; Kremer, Andreas; Mayo, Marlyn J.; Thuluvath, Paul J.; Levy, Cynthia; et al. (Journal of Hepatology, 2022)
Background & Aims: We examined the efficacy and safety of seladelpar, a selective peroxisome proliferator-activated receptor-delta agonist, in adults with primary biliary cholangitis (PBC) at risk of disease progression (alkaline phosphatase [ALP] ≥1.67xupper limit of normal [ULN]) who were receiving or intolerant to ursodeoxycholic acid. Methods: In this 52-week, phase II, dose-ranging, open-label study, patients were randomized (1:1) to seladelpar 5 mg/day (n = 53) or 10 mg/day (n = 55) or assigned to 2 mg/day (n = 11; United Kingdom sites after interim analysis) for 12 weeks. Doses could then be uptitrated to 10 mg/day. The primary efficacy endpoint was ALP change from baseline to Week 8. Results: Mean baseline ALP was 300, 345, and 295 U/L in the 2 mg, 5 mg, and 10 mg cohorts, respectively. Twenty-one percent of patients had cirrhosis, 71% had pruritus. At Week 8, mean ± standard error ALP reductions from baseline were 26 ± 2.8%, 33 ± 2.6%, and 41 ± 1.8% in the 2 mg (n = 11), 5 mg (n = 49), and 10 mg (n = 52) cohorts (all p ≤0.005), respectively. Responses were maintained or improved at Week 52, after dose escalation in 91% and 80% of the 2 mg and 5 mg cohorts, respectively. At Week 52, composite response (ALP <1.67xULN, ≥15% ALP decrease, and normal total bilirubin) rates were 64%, 53%, and 67%, and ALP normalization rates were 9%, 13%, and 33% in the 2 mg, 5 mg, and 10 mg cohorts, respectively. Pruritus visual analog scale score was decreased in the 5 mg and 10 mg cohorts. There were no treatment-related serious adverse events, and 4 patients discontinued due to adverse events. Conclusions: Seladelpar demonstrated robust, dose-dependent, clinically significant, and durable improvements in biochemical markers of cholestasis and inflammation in patients with PBC at risk of disease progression. Seladelpar appeared safe and well tolerated and was not associated with any increase in pruritus. ClinicalTrials.gov Number: NCT02955602 Clinicaltrialsregister.eu Number: 2016-002996-91 Lay summary: Current treatment options for patients living with primary biliary cholangitis (PBC) are not optimal due to inadequate effectiveness or undesirable side effects. Patients with PBC who took seladelpar, a new treatment being developed for PBC, at increasing doses (2, 5, or 10 mg/day) for 1 year had clinically significant, dose-dependent improvements in key liver tests. Treatment appeared safe and was not associated with any worsening in patient self-reported itch scores.
CRIS-Team Scopus Importer:2022-05-13
Keywords: Clinical study; Primary biliary cholangitis; Seladelpar

Autotaxin activity has a high accuracy to diagnose intrahepatic cholestasis of pregnancy - Kremer, Andreas; Bolier, Ruth; Dixon, Peter H.; Geenes, Victoria; Chambers, Jenny; Tolenaars, Dagmar; Ris-Stalpers, Carrie; Kaess, Bernhard M.; Rust, Christian; Van Der Post, Joris A.; Williamson, Catherine; Beuers, Ulrich; et al. (Journal of Hepatology, 2015)
Intrahepatic cholestasis of pregnancy (ICP) is defined by pruritus, elevated total fasting serum bile salts (TBS) and transaminases, and an increased risk of adverse fetal outcome. An accurate diagnostic marker is needed. Increased serum autotaxin correlates with cholestasis-associated pruritus. We aimed at unraveling the diagnostic accuracy of autotaxin in ICP.Serum samples and placental tissue were collected from 44 women with uncomplicated pregnancies and 105 with pruritus and/or elevated serum transaminases. Autotaxin serum levels were quantified enzymatically and by Western blotting, autotaxin gene expression by quantitative PCR.Serum autotaxin was increased in ICP (mean ± SD: 43.5 ± 18.2 nmol ml(-1)min(-1), n=55, p<0.0001) compared to other pruritic disorders of pregnancy (16.8 ± 6.7 nmol ml(-1)min(-1), n=33), pre-eclampsia complicated by HELLP-syndrome (16.8 ± 8.9 nmol ml(-1)min(-1), n=17), and pregnant controls (19.6 ± 5.7 nmol ml(-1)min(-1), n=44). Longitudinal analysis during pregnancy revealed a marked rise in serum autotaxin with onset of ICP-related pruritus. Serum autotaxin was increased in women taking oral contraceptives. Increased serum autotaxin during ICP was not associated with increased autotaxin mRNA in placenta. With a cut-off value of 27.0 nmol ml(-1)min(-1), autotaxin had an excellent sensitivity and specificity in distinguishing ICP from other pruritic disorders or pre-eclampsia/HELLP-syndrome. Serum autotaxin displayed no circadian rhythm and was not influenced by food intake.Increased serum autotaxin activity represents a highly sensitive, specific and robust diagnostic marker of ICP, distinguishing ICP from other pruritic disorders of pregnancy and pregnancy-related liver diseases. Pregnancy and oral contraception increase serum autotaxin to a much lesser extent than ICP.
EVALuna2:2015

Autotaxin activity predicts transplant-free survival in primary sclerosing cholangitis - Dhillon, Amandeep K.; Kremer, Andreas; Kummen, Martin; Boberg, Kirsten M.; Elferink, Ronald P.Oude; Karlsen, Tom H.; Beuers, Ulrich; Vesterhus, Mette; Hov, Johannes R. (Scientific Reports, 2019)
Autotaxin has been associated with liver disease severity and transplant-free survival. This study aimed to validate autotaxin as a biomarker in two cohorts of Norwegian large-duct PSC patients, one discovery panel (n = 165) and one validation panel (n = 87). Serum activity of autotaxin was measured in diluted sera by a fluorometric enzymatic assay. Patients reaching an end-point, liver transplantation or death, (discovery panel: n = 118 [71.5%]; validation panel: n = 35 [40.2%]), showed higher autotaxin activity compared with the other patients, P < 0.001 and P = 0.004, respectively. Kaplan-Meier survival analyses showed a strong association between increasing autotaxin activity and shorter liver transplant-free survival (discovery panel: P < 0.001, validation panel: P = 0.001). There was no relationship between autotaxin activity and the presence of inflammatory bowel disease or occurrence of hepatobiliary malignancy. In a multivariable analysis, high autotaxin activity was associated with an increased risk of liver transplantation or death (hazard ratio 2.03 (95% confidence interval 1.21–3.40), P < 0.01), independent from Mayo risk score, an in-house enhanced liver fibrosis score and interleukin-8 in serum. In conclusion, increased serum autotaxin activity is associated with reduced liver transplant-free survival independent from Mayo risk score and markers of inflammation and fibrosis.
CRIS-Team Scopus Importer:2019-06-21

Beyond the border: The use of lenvatinib in advanced hepatocellular carcinoma after different treatment lines: A retrospective analysis - Jefremow, Andre; Wiesmüller, Marco; Rouse, R. A.; Dietrich, Peter; Kremer, Andreas; Waldner, Maximilian; Neurath, Markus; Siebler, Jürgen (Journal of Physiology and Pharmacology, 2020)
The systemic treatment of unresectable hepatocellular carcinoma (HCC) has been improved throughout the past years. Different tyrosine kinase inhibitors (TKI) and checkpoint inhibitors have approval for first-and second-line treatment. Still, data are missing about the choice for the right agent and senseful therapy sequences. Between 2017 and 2019 we treated 149 HCC patients. From those, we identified the patients, who received lenvatinib either as a first-line treatment or in a later treatment line. We investigated seven patients retrospectively, who received lenvatinib in second, third, or fourth treatment line regarding efficacy and safety. Besides that, we compared those patients with 13 patients, who received lenvatinib as a first-line treatment regarding duration of therapy, overall survivial (OS), side effects and best response to treatment. We discovered remission (PR) showed 4/7, stable disease (SD) 2/7 and 1/7 mixed response with an overall tolerable safety profile in patients with a later line lenvatinib treatment. The duration and overall survival for therapy is similar in first-and later treatment lines with comparable results. Most side effects are moderate in each treatment line. Remarkably, on patient diagnoses with HCC (the Barcelona Clinic Liver Cancer C algorithm), who received lenvatinib in fourth line reached 67 months OD since diagnosis. We conclude, that lenvatinib could be considered as a treatment option of HCC for later treatment lines.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Advanced hepatocellular carcinoma; Lenvatinib; Liver cancer; Sequence therapy; Systemic treatment; Treatment lines; Tyrosine kinase inhibitors

Bile salt subspecies activate MRGX4 expressed on sensory neurons and cause itching in humans - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-25

Can genetic testing guide the therapy of cholestatic pruritus? A case of benign recurrent intrahepatic cholestasis type 2 with severe nasobiliary drainage-refractory itch - Holz, Robert; Kremer, Andreas; Luetjohann, Dieter; Wasmuth, Hermann E.; Lammert, Frank; Krawczyk, Marcin (Hepatology Communications, 2018)
Benign recurrent intrahepatic cholestasis (BRIC) is a peculiar familial disease caused by mutations of the genes encoding hepatocanalicular flippase for phosphatidylserine (ATP8B1; BRIC type 1) or the bile salt export pump (ABCB11; BRIC type 2). Here, we report on a patient with nasobiliary drainage-refractory BRIC type 2 who improved under plasma separation and anion absorption therapy. We also suggest that nasobiliary drainage might be an ineffective approach in carriers of severe loss-of-function mutations of the bile salt export pump ABCB11. (Hepatology Communications 2018;2:152-154).
EVALuna2:208322

Cellular and humoral immune responses to SARS-CoV-2 vaccination in patients after CD19.CAR T-cell therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Jacobs, Benedikt; Eisenhauer, Nina; Kämpf, Alina; Rösler, Wolf; Kharboutli, Soraya; Mougiakakos, Dimitrios; Lang, Vanessa; et al. (Blood Advances, 2023)
EVALuna2:512817

Characterization and treatment of persistent hepatocellular secretory failure - Van Dijk, Remco; Kremer, Andreas; Smit, Wouter; Van Den Elzen, Bram; Van Gulik, Thomas; Gouma, Dirk; Lameris, Johan S.; Bikker, Hennie; Enemuo, Valentine; Stokkers, Pieter C. F.; Feist, Mark; Bosma, Piter; et al. (Liver International, 2015)
Hepatocellular secretory failure induced by drugs, toxins or transient biliary obstruction may sometimes persist for months after removal of the initiating factor and may then be fatal without liver transplantation. We characterized patients with severe persistent hepatocellular secretory failure (PHSF) and treated them with the pregnane X receptor (PXR) agonist, rifampicin. We also studied the effect of rifampicin on PXR-dependent expression of genes involved in biotransformation and secretion in vitro.Thirteen patients (age 18-81 years, 6 male) with hepatocellular secretory failure that persisted after removal of the inducing factor (drugs/toxin: 9) or biliary obstruction (4) were identified over 6 years. Six of these patients were screened for ATP8B1 or ABCB11 mutations. All were treated with rifampicin (300 mg daily) for 1-10 weeks. Expression of genes involved in biotransformation and secretion was determined by rtPCR in human hepatocytes and intestinal cells incubated with rifampicin (10 ?mol/L).Serum bilirubin of patients with PHSF ranged from 264 to 755 ?mol/L. Normal ?GT was found in 10/13 patients of whom 3/6 tested positive for ATP8B1/ABCB11 mutations. Serum bilirubin declined to <33 ?mol/L after 1-10 weeks of rifampicin treatment. In vitro, rifampicin PXR-dependently upregulated biotransformation phase 1 (CYP3A4), phase 2 (UGT1A1) and phase 3 (MRP2) enzymes/carriers as well as the basolateral bile salt exporter OST?.Persistent hepatocellular secretory failure may develop in carriers of transporter gene mutations. In severe cases, rifampicin may represent an effective therapeutic option of PHSF. PXR-dependent induction of CYP3A4, UGT1A1, MRP2 and OST? could contribute to the anticholestatic effect of rifampicin in PHSF.
EVALuna2:1999

Chronic Pruritus in the Absence of Skin Disease: Pathophysiology, Diagnosis and Treatment - Pereira, Manuel P.; Kremer, Andreas; Mettang, Thomas; Staender, Sonja (American Journal of Clinical Dermatology, 2016)
Chronic pruritus arises not only from dermatoses, but also, in up to half of cases, from extracutaneous origins. A multitude of systemic, neurological, psychiatric, and somatoform conditions are associated with pruritus in the absence of skin disease. Moreover, pruritus is a frequently observed side effect of many drugs. It is therefore difficult for physicians to make a correct diagnosis. Chronic pruritus patients frequently present to the dermatologist with skin lesions secondary to a long-lasting scratching behavior, such as lichenification and prurigo nodularis. A structured clinical history and physical examination are essential in order to evaluate the pruritus, along with systematic, medical history-adapted laboratory and radiological tests carried out according to the differential diagnosis. For therapeutic reasons, a symptomatic therapy should be promptly initiated parallel to the diagnostic procedures. Once the underlying factor(s) leading to the pruritus are identified, a targeted therapy should be implemented. Importantly, the treatment of accompanying disorders such as sleep disturbances or mental symptoms should be taken into consideration. Even after successful treatment of the underlying cause, pruritus may persist, likely due to chronicity processes including peripheral and central sensitization or impaired inhibition at spinal level. A vast arsenal of topical and systemic agents targeting these pathophysiological mechanisms has been used to deter further chronicity. The therapeutic options currently available are, however, still insufficient for many patients. Thus, future studies aiming to unveil the complex mechanisms underlying chronic pruritus and develop new therapeutic agents are urgently needed.
EVALuna2:2197

Chronic pruritus represents a major burden in non-cholestatic hepatobiliary disorders - Düll, Miriam; Karlen, Vanessa; Vetter, Marcel; Dietrich, Peter; Kupfer, Joerg; Neurath, Markus; Kremer, Andreas (JOURNAL OF HEPATOLOGY, 2022)
CRIS-Team WoS Importer:2022-08-12

Chronischer Pruritus - Kremer, Andreas (Medizinische Monatsschrift für Pharmazeuten, 2019)
Chronic pruritus is an agonizing Symptom accompanying various diseases which often represents an interdisciplinary diagnostic and therapeutic challenge. Approxi-mately 15 % of the population suffers from this symptom. Aside general measures such as a cold surrounding and topical treatment, several systemic therapies such as anticonvulsives and antidepressants may be used in different pruritus-associated diseases due to similar chronification mechanisms. Novel insights into the neuro-biological mechanisms of chronic pruritus have led to new therapeutic approaches. Still we are currently far away from an optimal care of patients suffering from chronic pruritus.
CRIS-Team Scopus Importer:2021-04-20

Circulating Adaptive Immune Cells Expressing the Gut Homing Marker α4β7 Integrin Are Decreased in COVID-19 - Müller, Tanja; Becker, Elisabeth; Wiendl, Maximilian; Schulze, Lisa; Voskens, Caroline; Kremer, Andreas; Neurath, Markus; Zundler, Sebastian; Völkl, Simon (Frontiers in Immunology, 2021)
Background: Infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a wide range of symptoms including gastrointestinal manifestations, and intestinal epithelial cells are a target of the virus. However, it is unknown how the intestinal immune system contributes to systemic immune responses in coronavirus disease 2019 (COVID-19). Methods: We characterized peripheral blood lymphocytes from patients with active COVID-19 and convalescent patients as well as healthy controls by flow cytometry. Results: The frequency and absolute number of circulating memory T and B cells expressing the gut homing integrin α4β7 integrin was reduced during COVID-19, whether gastrointestinal symptoms were present or not. While total IgA-expressing B cells were increased, gut-imprinted B cells with IgA expression were stable. Conclusion: COVID-19 is associated with a decrease in circulating adaptive immune cells expressing the key gut homing marker α4β7 suggesting that these cells are preferentially recruited to extra-intestinal tissues independently of α4β7 or that the systemic immune response against SARS-CoV-2 is at least numerically dominated by extraintestinal, particularly pulmonary, immune cell priming.
CRIS-Team Scopus Importer:2021-05-21
Keywords: COVID-19; gut homing; integrins; SARS-CoV-2 infection; T cell trafficking

CLINICAL AND VIROLOGICAL CHARACTERISTICS AND RETREATMENT OF HCV-INFECTED PATIENTS WITH FAILURE TO MULTIPLE SUBSEQUENT DAA THERAPIES - Dietz, Julia; Vermehren, Johannes; Peiffer, Kai-Henrik; Wietzke-Braun, Perdita; Muellhaupt, Beat; Schattenberg, Joern; Antoni, Christoph; Hametner, Stephanie; Mauss, Stefan; Heinzow, Hauke; Graf, Christiana; Port, Kerstin; et al. (HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-25

Clinical management of pruritus - Staender, Sonja; Zeidler, Claudia; Magnolo, Nina; Raap, Ulrike; Mettang, Thomas; Kremer, Andreas; Weisshaar, Elke; Augustin, Matthias (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
The care of patients with chronic pruritus as a symptom of a wide variety of underlying diseases continues to confront dermatologists with diagnostic and therapeutic challenges. However, a structured history and a physical examination may already substantially help in narrowing down the number of potential differential diagnoses. Apart form reducing the intensity of pruritus, identification and appropriate treatment of the underlying disease are important needs of patients. If these goals doesn't lead to improvement of itch, current guidelines provide a number of topical and systemic therapies for symptomatic treatment. Various skin lesions (for example, xerosis caused by irritant substances, secondary scratch lesions) prompt patients to consult a dermatologist, but most cases require an interdisciplinary therapeutic approach to identify potential internal medicine, neurologic, or psychosomatic aspects. Although great strides have been made in basic research, specific therapies are still rare, and a precise knowledge of the legal framework for the implementation of guidelines (for example, off-label use) is essential. This CME article gives an overview of the causes of and treatment options for chronic pruritus and discusses both advances in basic research as well as progress in clinical knowledge.
EVALuna2:1994

Combined de‐repression of chemoresistance associated mitogen‐activated protein kinase 14 and activating transcription factor 2 by loss of microrna‐622 in hepatocellular carcinoma - Fritz, Valerie; Malek, Lara; Gaza, Anne; Wormser, Laura; Appel, Majken; Kremer, Andreas; Thasler, Wolfgang E.; Neurath, Markus; Hellerbrand, Claus; Boßerhoff, Anja Katrin; Dietrich, Peter; Siebler, Jürgen (Cancers, 2021)
Chemoresistance is a major hallmark driving the progression and poor prognosis of hepatocellular carcinoma (HCC). Limited chemoresponse of HCC was demonstrated to be mediated by mitogen‐activated protein kinase 14 (MAPK14) and activating transcription factor 2 (ATF2). Recently, we have demonstrated loss of control of RAS‐RAF‐ERK‐signaling as a consequence of miR‐622 downregulation in HCC. However, the majority of target genes of this potent tumorsuppressive microRNA had remained elusive. The MAPK14‐ATF2‐axis represents a collateral pathway ensuring persisting ERK‐activation in the presence of sorafenib‐mediated RAF-inhibition. In contrast to the function of the MAPK14‐ATF2‐axis, both the expression and regulation of MAPK14 and ATF2 in human HCC remained to be clarified. We found combined overexpression of MAPK14 and ATF2 in human HCC cells, tissues and in sorafenib resistant cell lines. High expression of MAPK14 and ATF2 was associated with reduced overall survival in HCC patients. Deciphering the molecular mechanism promoting combined upregulation of MAPK14 and ATF2 in HCC, we revealed that miR‐622 directly targets both genes, resulting in combined de‐repression of the MAPK14‐ATF2‐axis. Together, miR‐622 represents a superior regulator of both RAS‐RAF‐ERK as well as MAPK14‐ATF2‐signaling pathways in liver cancer.
CRIS-Team Scopus Importer:2021-03-19
Keywords: HCC; Hepatocellular carcinoma; Liver cancer; MAPK14; MicroRNA; MiR‐622; RAS

Complementary roles of murine NaV1.7, NaV1.8 and NaV1.9 in acute itch signalling - Kühn, Helen; Kappes, Leonie; Wolf, Katharina; Gebhardt, Lisa; Neurath, Markus; Reeh, Peter; Fischer, Michael J.M.; Kremer, Andreas (Scientific Reports, 2020)
Acute pruritus occurs in various disorders. Despite severe repercussions on quality of life treatment options remain limited. Voltage-gated sodium channels (NaV) are indispensable for transformation and propagation of sensory signals implicating them as drug targets. Here, NaV1.7, 1.8 and 1.9 were compared for their contribution to itch by analysing NaV-specific knockout mice. Acute pruritus was induced by a comprehensive panel of pruritogens (C48/80, endothelin, 5-HT, chloroquine, histamine, lysophosphatidic acid, trypsin, SLIGRL, β-alanine, BAM8-22), and scratching was assessed using a magnet-based recording technology. We report an unexpected stimulus-dependent diversity in NaV channel-mediated itch signalling. NaV1.7−/− showed substantial scratch reduction mainly towards strong pruritogens. NaV1.8−/− impaired histamine and 5-HT-induced scratching while NaV1.9 was involved in itch signalling towards 5-HT, C48/80 and SLIGRL. Furthermore, similar microfluorimetric calcium responses of sensory neurons and expression of itch-related TRP channels suggest no change in sensory transduction but in action potential transformation and conduction. The cumulative sum of scratching over all pruritogens confirmed a leading role of NaV1.7 and indicated an overall contribution of NaV1.9. Beside the proposed general role of NaV1.7 and 1.9 in itch signalling, scrutiny of time courses suggested NaV1.8 to sustain prolonged itching. Therefore, NaV1.7 and 1.9 may represent targets in pruritus therapy.
CRIS-Team Scopus Importer:2020-02-21

Correction to: Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections (European Journal of Clinical Microbiology & Infectious Diseases, (2021), 10.1007/s10096-021-04285-4) - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
In the originally published version of the article, captions of Figures 1, 2, 3, 4, and 5 have missing figure denominations. The figures are presented here with correct captions. Layout adjustments are also made to Tables 2-5 for readability. The original article has been corrected. (Figure presented.).
CRIS-Team Scopus Importer:2021-07-30

Deciphering the role of HLA-DO in immune responses after allogeneic stem cell transplantation - Zeun, Julia; Flamann, Cindy; Neubeck, S.; Bausenwein, J.; Seyler, L.; Vogler, T.; Brey, Stefanie; Büttner-Herold, Maike; Hildner, Kai; Winkler, Thomas; Bruns, Heiko; Kretschmann, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS-CoV-2 antibody assays are used for epidemiological studies and for the assessment of vaccine responses in highly vulnerable patients. So far, data on cross-reactivity of SARS-CoV-2 antibody assays is limited. Here, we compared four enzyme-linked immunosorbent assays (ELISAs; Vircell SARS-CoV-2 IgM/IgA and IgG, Euroimmun SARS-CoV-2 IgA and IgG) for detection of anti-SARS-CoV-2 antibodies in 207 patients with COVID-19, 178 patients with serological evidence of different bacterial infections, 107 patients with confirmed viral respiratory disease, and 80 controls from the pre-COVID-19 era. In COVID-19 patients, the assays showed highest sensitivity in week 3 (Vircell-IgM/A and Euroimmun-IgA: 78.9% each) and after week 7 (Vircell-IgG: 97.9%; Euroimmun-IgG: 92.1%). The antibody indices were higher in patients with fatal disease. In general, IgM/IgA assays had only limited or no benefit over IgG assays. In patients with non-SARS-CoV-2 respiratory infections, IgG assays were more specific than IgM/IgA assays, and bacterial infections were associated with more false-positive results than viral infections. The specificities in bacterial and viral infections were 68.0 and 81.3% (Vircell-IgM/IgA), 84.8 and 96.3% (Euroimmun-IgA), 97.8 and 86.0% (Vircell-IgG), and 97.8 and 99.1% (Euroimmun-IgG), respectively. Sera from patients positive for antibodies against Mycoplasma pneumoniae, Chlamydia psittaci, and Legionella pneumophila yielded particularly high rates of unspecific false-positive results in the IgM/IgA assays, which was revealed by applying a highly specific flow-cytometric assay using HEK 293 T cells expressing the SARS-CoV-2 spike protein. Positive results obtained with anti-SARS-CoV-2 IgM/IgA ELISAs require careful interpretation, especially if there is evidence for prior bacterial respiratory infections.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Antibody; Bacterial infections; Coronavirus; COVID-19; Euroimmun; SARS-CoV-2; Vircell

Discovery and Differential Processing of HLA Class II-Restricted Minor Histocompatibility Antigen LB-PIP4K2A-1S and Its Allelic Variant by Asparagine Endopeptidase - Kremer, Anita; Bausenwein, Judith; Lurvink, Ellie; Kremer, Andreas; Rutten, Caroline E.; van Bergen, Cornelis A.M.; Kretschmann, Sascha; van der Meijden, Edith; Honders, Maria W.; Mazzeo, Daniela; Watts, Colin; Mackensen, Andreas; et al. (Frontiers in Immunology, 2020)
Minor histocompatibility antigens are the main targets of donor-derived T-cells after allogeneic stem cell transplantation. Identification of these antigens and understanding their biology are a key requisite for more insight into how graft vs. leukemia effect and graft vs. host disease could be separated. We here identified four new HLA class II-restricted minor histocompatibility antigens using whole genome association scanning. For one of the new antigens, i.e., LB-PIP4K2A-1S, we measured strong T-cell recognition of the donor variant PIP4K2A-1N when pulsed as exogenous peptide, while the endogenously expressed variant in donor EBV-B cells was not recognized. We showed that lack of T-cell recognition was caused by intracellular cleavage by a protease named asparagine endopeptidase (AEP). Furthermore, microarray gene expression analysis showed that PIP4K2A and AEP are both ubiquitously expressed in a wide variety of healthy tissues, but that expression levels of AEP were lower in primary acute myeloid leukemia (AML). In line with that, we confirmed low activity of AEP in AML cells and demonstrated that HLA-DRB1*03:01 positive primary AML expressing LB-PIP4K2A-1S or its donor variant PIP4K2A-1N were both recognized by specific T-cells. In conclusion, LB-PIP4K2A-1S not only represents a novel minor histocompatibility antigen but also provides evidence that donor T-cells after allogeneic stem cell transplantation can target the autologous allelic variant as leukemia-associated antigen. Furthermore, it demonstrates that endopeptidases can play a role in cell type-specific intracellular processing and presentation of HLA class II-restricted antigens, which may be explored in future immunotherapy of AML.
CRIS-Team Scopus Importer:2020-04-07
Keywords: allogeneic stem cell transplantation; CD4 T-cells; graft vs. leukemia effect; HLA class II; minor histocompatibility antigens

Does the Beneficial Antipruritic Effect of Bezafibrate in Primary Biliary Cholangitis Depend on Autotaxin Activity? - Kremer, Andreas; Le Cleac'H, Aline; Wolf, Katharina; Chazouilleres, Olivier; Lemoinne, Sara; De Chaisemaitin, Luc; Chollet-Martin, Sylvie; Humbert, Lydie; Rainteauu, Dominique; Poupon, Raoul; Rousseau, Alexandra; Corpechot, Christophe (2018)
EVALuna2:35137

Effect of Seladelpar on Pruritus in Primary Biliary Cholangitis: 26-Week Analysis of an Ongoing International, randomized, Dose Ranging Phase 2 Study - Kremer, Andreas; Bowlus, Christopher L.; Neff, Guy W.; Aspinall, Richard; Galambos, Michael R.; Goel, Aparna; Hirschfield, Gideon; Mayo, Marlyn J.; Swain, Mark Gordon; Borg, Brian; Doerffel, Yvonne; Gordon, Stuart C.; et al. (2018)
EVALuna2:35128

Effects of Vedolizumab in Patients With Primary Sclerosing Cholangitis and Inflammatory Bowel Diseases - Lynch, Kate D.; Chapman, Roger W.; Keshav, Satish; Montano-Loza, Aldo J.; Mason, Andrew L.; Kremer, Andreas; Vetter, Marcel; De Krijger, Manon; Ponsioen, Cyriel Y.; Trivedi, Palak; Hirschfield, Gideon; Schramm, Christoph; et al. (Clinical Gastroenterology and Hepatology, 2020)
BACKGROUND & AIMS: Gut-homing lymphocytes that express the integrin alpha 4 beta 7 and CCR9 might contribute to development of primary sclerosing cholangitis (PSC). Vedolizumab, which blocks the integrin alpha 4 beta 7, is used to treat patients with inflammatory bowel diseases (IBD), but there are few data on its efficacy in patients with PSC. We investigated the effects of vedolizumab in a large international cohort of patients with PSC and IBD.
CRIS-Team WoS Importer:2020-01-03

Efficacy and safety of immune checkpoint inhibitor rechallenge in individuals with hepatocellular carcinoma - Scheiner, Bernhard; Roessler, Daniel; Phen, Samuel; Lim, Mir; Pomej, Katharina; Pressiani, Tiziana; Cammarota, Antonella; Fründt, Thorben W.; von Felden, Johann; Schulze, Kornelius; Himmelsbach, Vera; Finkelmeier, Fabian; et al. (JHEP Reports, 2023)
Background & Aims: We investigated the efficacy and safety of immune checkpoint inhibitor (ICI) rechallenge in patients with hepatocellular carcinoma (HCC) who received ICI-based therapies in a previous systemic line. Methods: In this international, retrospective multicenter study, patients with HCC who received at least two lines of ICI-based therapies (ICI-1, ICI-2) at 14 institutions were eligible. The main outcomes included best overall response and treatment-related adverse events. Results: Of 994 ICI-treated patients screened, a total of 58 patients (male, n = 41; 71%) with a mean age of 65.0±9.0 years were included. Median systemic treatment lines of ICI-1 and ICI-2 were 1 (range, 1-4) and 3 (range, 2-9), respectively. ICI-based therapies used at ICI-1 and ICI-2 included ICI alone (ICI-1, n = 26, 45%; ICI-2, n = 4, 7%), dual ICI regimens (n = 1, 2%; n = 12, 21%), or ICI combined with targeted therapies/anti-VEGF (n = 31, 53%; n = 42, 72%). Most patients discontinued ICI-1 due to progression (n = 52, 90%). Objective response rate was 22% at ICI-1 and 26% at ICI-2. Responses at ICI-2 were also seen in patients who had progressive disease as best overall response at ICI-1 (n = 11/21; 52%). Median time-to-progression at ICI-1 and ICI-2 was 5.4 (95% CI 3.0-7.7) months and 5.2 (95% CI 3.3-7.0) months, respectively. Treatment-related adverse events of grade 3-4 at ICI-1 and ICI-2 were observed in 9 (16%) and 10 (17%) patients, respectively. Conclusions: ICI rechallenge was safe and resulted in a treatment benefit in a meaningful proportion of patients with HCC. These data provide a rationale for investigating ICI-based regimens in patients who progressed on first-line immunotherapy in prospective trials. Impact and implications: Therapeutic sequencing after first-line immune checkpoint inhibitor (ICI)-based therapy for advanced hepatocellular carcinoma (HCC) remains a challenge as no available second-line treatment options have been studied in immunotherapy-pretreated patients. Particularly, the role of ICI rechallenge in patients with HCC is unclear, as data from prospective trials are lacking. We investigated the efficacy and safety of ICI-based regimens in patients with HCC pretreated with immunotherapy in a retrospective, international, multicenter study. Our data provide the rationale for prospective trials investigating the role of ICI-based regimens in patients who have progressed on first-line immunotherapy.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Immune checkpoint blocker; Immunotherapy; Liver cancer; Systemic therapy

Efficacy and Safety of Seladelpar, a Selective Peroxisome Proliferator-Activated Receptor Delta Agonist, in Primary Biliary Cholangitis: 52-Week Analysis of an Ongoing International, Randomized, Dose Ranging Phase 2 Study - Bowlus, Christopher L.; Neff, Guy W.; Aspinall, Richard; Galambos, Michael R.; Goel, Aparna; Hirschfield, Gideon; Kremer, Andreas; Mayo, Marlyn J.; Swain, Mark Gordon; Borg, Brian; Doerffel, Yvonne; Gordon, Stuart C.; et al. (2018)
EVALuna2:207767

Efficacy of GKT831 in patients with primary biliary cholangitis and inadequate response to ursodeoxycholic acid: Interim efficacy results of a phase 2 clinical trial - Dalekos, George; Invernizzi, Pietro; Nevens, Frederik; Hans, Van Vlierberghe; Zigmond, Ehud; Andrade, Raul J.; Ben Ari, Ziv; Heneghan, Michael; Huang, Jonathan; Harrison, Stephen; Minuk, Gerald; Joern, Schattenberg; et al. (JOURNAL OF HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-05-07

Efficiency and Toxicity of Lenvatinib in Advanced HCC in Later Treatment Lines - Jefremow, Andre; Wiesmüller, Marco; Rouse, Rachel Amanda; Dietrich, Peter; Kremer, Andreas; Waldner, Maximilian; Neurath, Markus; Siebler, Jürgen (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Elevated liver function readings: Drugs as important trigger Arzneimittel als wichtige Auslöser - Düll, Miriam; Kremer, Andreas (Pharmazeutische Zeitung, 2020)
CRIS-Team Scopus Importer:2024-12-16

Empfohlene Diagnostik bei Pruritus auf primär unveränderter Haut - Düll, Miriam; Kremer, Andreas (Die Dermatologie, 2024)
Background: Chronic pruritus affecting primary non-lesional skin (CPNL) manifests as a common symptom across a spectrum of diseases spanning various medical specialties. Given the diverse etiological factors involved, diagnosing the underlying condition poses a significant challenge. Objectives: To provide a comprehensive overview of clinical, laboratory, and imaging diagnostics for CPNL. Materials and methods: A thorough literature search on the diagnostics of chronic pruritus was conducted using PubMed with specific keywords “chronic pruritus AND non-lesional skin”, “chronic itch AND non-lesional skin”, “chronic pruritus AND diagnostics”, “chronic itch AND diagnostics”, “CKD-aP”, “hepatic pruritus”, “cholestatic pruritus”, and “myeloproliferative neoplasms AND pruritus”. Results: A systematic diagnostic approach is recommended for patients with CPNL, guided by the prevalence of pruritus-associated diseases. Initial basic diagnostics facilitate a cost-effective and focused evaluation during the initial medical assessment. Information pertaining to underlying diseases can be further refined through specialized diagnostic procedures. Conclusions: CPNL often presents a diagnostic dilemma. Adopting a stepwise diagnostic strategy facilitates the identification of underlying etiologies, which is crucial for recognizing diseases and administering pruritus-specific pharmacotherapy.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Basic diagnostic workup; Itch; Liver; Myeloproliferative neoplasms; Stepwise diagnostic strategy

Endogenous Opioid Levels Do Not Correlate With Itch Intensity and Therapeutic Interventions in Hepatic Pruritus - Düll, Miriam; Wolf, Katharina; Vetter, Marcel; Dietrich, Peter; Neurath, Markus; Kremer, Andreas (Frontiers in Medicine, 2021)
Background: Chronic pruritus affects up to 70% of patients with immune-mediated hepatobiliary disorders. Antagonists of the μ-opioid receptor (MOR) and agonists of the κ-opioid receptor (KOR) are used to treat hepatic itch, albeit with limited success. An imbalance between ligands of MOR and KOR receptors has recently been suggested as a potential mechanism of hepatic pruritus. In this study, we therefore investigated systemic levels of important endogenous opioids such as β-endorphin, dynorphin A, Leu- and Met-enkephalin in plasma of a large cohort of well-characterized patients with immune-mediated cholestatic disorders, including patients with liver cirrhosis, and during effective anti-pruritic therapy. Methods: Plasma samples and clinical data were prospectively collected from well-characterized patients with primary/secondary sclerosing cholangitis (PSC/SSC), primary biliary cholangitis (PBC) and overlap syndromes suffering from pruritus (n = 29) and age-, gender- and disease-matched controls without pruritus (n = 27) as well as healthy controls (n = 20). General laboratory testing for hepatobiliary and renal function was performed. Levels of β-endorphin, dynorphin A, Leu- and Met-enkephalin were quantified in plasma by ELISA. Intensity of pruritus over the last week was evaluated using a visual analog scale (VAS, 0–10). Results: PBC and PSC patients with or without pruritus did neither differ in disease entity, disease stage, nor in the presence of cirrhosis. While both dynorphin A and β-endorphin concentrations were lower in pruritic patients compared to those without pruritus and healthy controls, the MOR/KOR ligand ratio was unaltered. No significant differences were observed for Leu- and Met-enkephalin concentrations. Opioid levels correlated with neither itch intensity nor stage of disease. Cirrhotic patients displayed higher concentrations of MOR agonist Leu-enkephalin and KOR agonist dynorphin A. Endogenous opioid levels remained largely unchanged after successful treatment with the potent anti-pruritic drugs rifampicin and bezafibrate. Conclusions: Endogenous opioid levels and the MOR/KOR ligand ratio neither correlate with itch intensity nor differentiate pruritic from non-pruritic patients with immune-mediated liver diseases. Thus, endogenous opioids may modulate signaling pathways involved in hepatic pruritus, but are unlikely to represent the major pruritogens in liver disease.
CRIS-Team Scopus Importer:2021-05-14
Keywords: bezafibrate; cholestasis; dynorphin; endorphin; enkephalin; liver; rifampicin; therapy

Enteroendocrine cells are a potential source of serum autotaxin in men - Bolier, Ruth; Tolenaars, Dagmar; Kremer, Andreas; Saris, Job; Pares, Albert; Verheij, Joanne; Bosma, Piter J.; Beuers, Ulrich; Elferink, Ronald P. J. Oude (BBA - Biochimica et Biophysica Acta, 2016)
Serum autotaxin (ATX) activity is significantly increased in cholestatic patients. Our study aimed to unravel the source(s) of ATX in cholestasis.ATX activity and protein were measured in sera of healthy (n=33) and cholestatic patients (n=152), including women with intrahepatic cholestasis of pregnancy. ATX mRNA and protein expression were analyzed in various tissues from mice and men. Induction of ATX activity was assessed in mouse models of extrahepatic (bile duct ligation) and intrahepatic cholestasis (Atp8b1(G308V/G308V), 0.1% cholate-supplemented diet). ATX clearance in cholestatic and control mice was assessed after intravenous injection of recombinant ATX. Human hepatic clearance was estimated by comparing ATX activity in portal and hepatic vein serum.Serum ATX activity and ATX protein concentration tightly correlated under all conditions in patients and controls (p<0.0001). In humans Atx mRNA was highly expressed in small intestine, whereas in mice Atx was expressed mainly in brain and placenta but not in small intestine. Extensive ATX protein expression was identified in human, but not murine intestinal enteroendocrine cells. In murine models of cholestasis and cholestatic pregnancy plasma ATX activity was only mildly elevated (up to 2.1-fold). Atx tissue expression and rATX clearance after parenteral administration did not differ between cholestatic and control mice.Serum ATX activity during cholestasis and itch is enhanced by increased protein concentration rather than enzymatic induction. In mice, clearance of ATX is not affected by cholestasis. Small intestinal ATX expression by enteroendocrine cells might represent an important source of cholestasis-induced serum ATX activity in men.
EVALuna2:2087

Epithelia-Sensory Neuron Cross Talk Underlies Cholestatic Itch Induced by Lysophosphatidylcholine - Chen, Yong; Wang, Zi Long; Yeo, Michele; Zhang, Qiao Juan; López-Romero, Ana E.; Ding, Hui Ping; Zhang, Xin; Zeng, Qian; Morales-Lázaro, Sara L.; Moore, Carlene; Jin, Ying Ai; Yang, Huang He; et al. (Gastroenterology, 2021)
Background & Aims: Limited understanding of pruritus mechanisms in cholestatic liver diseases hinders development of antipruritic treatments. Previous studies implicated lysophosphatidic acid (LPA) as a potential mediator of cholestatic pruritus. Methods: Pruritogenicity of lysophosphatidylcholine (LPC), LPA's precursor, was examined in naïve mice, cholestatic mice, and nonhuman primates. LPC's pruritogenicity involving keratinocyte TRPV4 was studied using genetic and pharmacologic approaches, cultured keratinocytes, ion channel physiology, and structural computational modeling. Activation of pruriceptor sensory neurons by microRNA-146a (miR-146a), secreted from keratinocytes, was identified by in vitro and ex vivo Ca2+ imaging assays. Sera from patients with primary biliary cholangitis were used for measuring the levels of LPC and miR-146a. Results: LPC was robustly pruritic in mice. TRPV4 in skin keratinocytes was essential for LPC-induced itch and itch in mice with cholestasis. Three-dimensional structural modeling, site-directed mutagenesis, and channel function analysis suggested a TRPV4 C-terminal motif for LPC binding and channel activation. In keratinocytes, TRPV4 activation by LPC induced extracellular release of miR-146a, which activated TRPV1+ sensory neurons to cause itch. LPC and miR-146a levels were both elevated in sera of patients with primary biliary cholangitis with itch and correlated with itch intensity. Moreover, LPC and miR-146a were also increased in sera of cholestatic mice and elicited itch in nonhuman primates. Conclusions: We identified LPC as a novel cholestatic pruritogen that induces itch through epithelia-sensory neuron cross talk, whereby it directly activates skin keratinocyte TRPV4, which rapidly releases miR-146a to activate skin-innervating TRPV1+ pruriceptor sensory neurons. Our findings support the new concept of the skin, as a sensory organ, playing a critical role in cholestatic itch, beyond liver, peripheral sensory neurons, and central neural pathways supporting pruriception.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cholestatic Itch; Keratinocyte TRPV4; Lysophosphatidylcholine; miR-146a; TRPV1 Pruriceptor

EXPERT CONSENSUS CRITERIA AND PRACTICAL RECOMMENDATIONS FOR PBC CARE IN THE COVID-19 ERA AND BEYOND - Berenguer, Marina; Kremer, Andreas; Hirschfield, Gideon; Jones, David; Leroy, Vincent; Adekunle, Femi; Carbone, Marco (HEPATOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-03

Failure on voxilaprevir, velpatasvir, sofosbuvir and efficacy of rescue therapy - Dietz, Julia; Di Maio, Velia Chiara; de Salazar, Adolfo; Merino, Dolores; Vermehren, Johannes; Paolucci, Stefania; Kremer, Andreas; Lara, Magdalena; Pardo, Maria Rodriguez; Zoller, Heinz; Degasperi, Elisabetta; Peiffer, Kai Henrik; et al. (Journal of Hepatology, 2021)
Background & Aims: There are limited data on patients with chronic HCV infection in whom combination voxilaprevir (VOX), velpatasvir (VEL), sofosbuvir (SOF) retreatment fails. Thus, we aimed to assess treatment failure and rescue treatment options in these patients. Methods: Samples from 40 patients with HCV genotypes (GT) 1-4 in whom VOX/VEL/SOF retreatment failed were collected within the European Resistance Study Group. Population-based resistance analyses were conducted and clinical parameters and retreatment efficacies were evaluated retrospectively in 22 patients. Results: Most VOX/VEL/SOF failure patients were infected with HCV GT3a (n = 18, 45%) or GT1a (n = 11, 28%) and had cirrhosis (n = 28, 70%). Previous treatments included an NS3-inhibitor (30%), an NS5A-inhibitor (100%) and SOF (85%). Baseline RAS data from a subgroup of patients before VOX/VEL/SOF retreatment (78%) showed few NS3 RASs apart from Q80K in GT1a (40%), typical NS5A RAS patterns in most patients (74%) and no S282T in NS5B. Sequencing after VOX/VEL/SOF failure was available in 98% of patients and showed only minor changes for NS3 and NS5A RASs. In 22 patients, rescue treatment was initiated with glecaprevir, pibrentasvir alone (n = 2) or with SOF±ribavirin (n = 15), VOX/VEL/SOF±ribavirin (n = 4) or VEL/SOF and ribavirin (n = 1) for 12 to 24 weeks. Sustained virologic response was achieved in 15/19 (79%) patients with a final treatment outcome. Of these, 2 GT3a-infected patients had virologic failure after rescue treatment with VEL/SOF or glecaprevir/pibrentasvir+SOF+ribavirin, and 2 patients with cirrhosis died during treatment or before reaching SVR12. Conclusions: VOX/VEL/SOF failure was mainly observed in HCV GT3- and GT1a-infected patients with cirrhosis and was not associated with specific RAS patterns within NS3, NS5A or NS5B target regions. Rescue treatment with multiple targeted therapies was effective in most patients. Lay summary: The advent of direct-acting antivirals has enabled the effective cure of chronic hepatitis C in most patients. However, treatment failure occurs in some patients, who are often retreated with a combination regimen called VOX/VEL/SOF, which is associated with very high rates of cure. However, VOX/VEL/SOF retreatment also fails in some patients. Herein, we analysed samples from patients in whom VOX/VEL/SOF retreatment failed and we assessed the efficacy of different rescue therapies, showing that rescue treatment is effective in most patients (79%).
CRIS-Team Scopus Importer:2021-03-05
Keywords: DAA; Direct-acting antivirals; HCV; Hepatitis C virus; Rescue therapy; Resistance-associated substitutions; Voxilaprevir/velpatasvir/sofosbuvir

Fever of unknown origin following allogeneic stem cell transplantation - an unusual case - Meintker, Lisa; Kremer, Andreas; Brandt, Adrian; Spoerl, S.; Slanikova, A.; Mackensen, Andreas; Winkler, Julia; Rösler, Wolf (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Free-Breathing Low-Field MRI of the Lungs Detects Functional Alterations Associated With Persistent Symptoms After COVID-19 Infection. - Levy, Simon; Heiß, Rafael; Grimm, Robert; Grodzki, David; Hadler, Dominique; Voskrebenzev, Andreas; Vogel-Claussen, Jens; Fuchs, Florian; Strauss, Richard; Achenbach, Susanne; Hinsen, Maximilian; Klett, Daniel; et al. (Investigative Radiology, 2022)
OBJECTIVES: With the COVID-19 pandemic, repetitive lung examinations have become necessary to follow-up symptoms and associated alterations. Low-field MRI, benefiting from reduced susceptibility effects, is a promising alternative for lung imaging to limit radiations absorbed by patients during CT examinations, which also have limited capability to assess functional alterations. The aim of this investigative study was to explore the functional abnormalities that free-breathing 0.55 T MRI in combination with the phase-resolved functional lung (PREFUL) analysis could identify in patients with persistent symptoms after COVID-19 infection. MATERIALS AND METHODS: Seventy-four COVID-19 patients and 8 healthy volunteers were prospectively scanned in free-breathing with a balanced steady-state free-precession sequence optimized at 0.55 T, 5 months postinfection on average. Normalized perfusion (Q), fractional ventilation (FV), and flow-volume loop correlation (FVLc) maps were extracted with the PREFUL technique. Q, FV, and FVLc defects as well as defect overlaps between these metrics were quantified. Morphological turbo-spin-echo images were also acquired, and the extent of abnormalities was scored by a board-certified radiologist. To investigate the functional correlates of persistent symptoms, a recursive feature elimination algorithm was applied to find the most informative variables to detect the presence of persistent symptoms with a logistic regression model and a cross-validation strategy. All MRI metrics, sex, age, body mass index, and the presence of preexisting lung conditions were included. RESULTS: The most informative variables to detect persistent symptoms were the percentage of concurrent Q and FVLc defects and of areas free of those defects. A detection accuracy of 71.4% was obtained with these 2 variables when fitting the model on the entire dataset. Although none of the single variables differed between patients with and without persistent symptoms ( P > 0.05), the combined score of these 2 variables did ( P < 0.02). This score also showed a consistent increase from healthy volunteers (7.7) to patients without persistent symptoms (8.2) and with persistent symptoms (8.6). The morphological abnormality score showed poor correlation with the functional parameters. CONCLUSIONS: Functional pulmonary examinations using free-breathing 0.55 T MRI with PREFUL analysis revealed potential quantitative markers of impaired lung function in patients with persistent symptoms after COVID-19 infection, potentially complementing morphologic imaging. Future work is needed to explore the translational relevance and clinical implication of these findings.
EVALuna2:506323

Frequent Follow-Up of Delisted Liver Transplant Candidates Is Necessary: An Observational Study about Characteristics and Outcomes of Delisted Liver Transplant Candidates - Payani, Elnaz; Koliogiannis, Dionysios; Schoenberg, Markus Bo; Koch, Dominik; Eser-Valeri, Daniela; Denk, Gerald; Rehm, Markus; Schäfer, Simon; Ehmer, Ursula; Kremer, Andreas; Meiser, Bruno; Werner, Jens; et al. (Journal of Clinical Medicine, 2023)
This observational study focuses on the characteristics and survival of patients taken off of the liver transplant waiting list. Assessment of post-delisting survival and a frequent follow-up of patients after delisting are important keys to improve the survival rate of patients with liver failure after being delisted. Within this study, delisted liver transplant candidates were divided into the following groups: (1) “too good” (54%) or (2) “too sick” (22%) for transplantation, (3) adherence issues (12%) or (4) therapy goal changed (11%). The 5-year survival after delisting within these groups was 84%, 9%, 50%, and 68%, respectively. Less than 3% of the delisted patients had to be relisted again. The clinical expert decision of the multidisciplinary transplant team was sufficiently accurate to differentiate between patients requiring liver transplantation and those who were delisted after a stable recovery of liver function. The assessment of post-delisting survival may serve as a complementary metric to assess differences in center practices and to estimate cumulative post-delisting mortality risk.
CRIS-Team Scopus Importer:2023-10-06
Keywords: delisting; liver transplant waiting list; liver transplantation; transplant conference

Functional connectivity reveals altered activation of distinct brain areas in pruritus of cholestasis - Kremer, Andreas; Buchwald, Theresa; Vetter, Marcel; Dörfler, Arnd; Forster, Clemens (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

Generalized resistance to pruritogen-induced scratching in the C3H/HeJ strain - Zhang, Yanbin; Richter, Nicole; König, Christine; Kremer, Andreas; Zimmermann, Katharina (Frontiers in Molecular Neuroscience, 2022)
Previously the effect of the pruritogens, such as histamine and chloroquine, was tested in 11 inbred mouse strains, and this study aimed to identify resistant and sensitive strains, consistent with the observation that underlies the large variability in human populations. In the present study, we used the low responder C3H/HeJ (C3H) and the more sensitive C57BL/6J (C57) strain to find out if resistance and sensitivity to develop pruritus is restricted to only histamine and chloroquine or extends to other known pruritogens as well. We tested five additional commonly known pruritogens. We established dose-response relationships by injecting four concentrations of the pruritogens in the range of 0.3, 1, 3, and ten-fold in the nuchal fold. Then we assessed the scratching behavior for 30 min after injection with an automated custom-designed device based on the bilateral implantation of mini-magnets in the hind paws and on single cages placed within a magnetic coil. We found that the resistance to pruritogens is a general phenotype of the C3H strain and extends to all pruritogens tested, including not only histamine and chloroquine, but also endothelin, trypsin, 5-HT (serotonin), the short peptide SLIGRL, and Lysophosphatidic acid (LPA). C57 was more sensitive to all pruritogens and, in contrast to C3H, dose-response relationships were evident for some of the pruritogens. In general, comparable peak scratch responses were observed for the 0.3-fold concentrations of the pruritogens in C57 whereas C3H required at least the ten-fold concentration and still displayed only between 5 and 33% of the scratch responses observed in C57 for the respective pruritogen. The general resistance to pruritogens and the low level of scratching behavior found in the C3H strain is an interesting trait and represents a model for the study of the heritability of itch. It is accompanied in C3H with a higher sensitivity in assays of nociception.
CRIS-Team Scopus Importer:2022-11-04
Keywords: C57BL/6J; heritability; inbred mouse strains; itch; pruritus; scratching behavior

GLIMMER: A Randomized Phase 2b Dose-Ranging Trial of Linerixibat in Primary Biliary Cholangitis Patients With Pruritus - Levy, Cynthia; Kendrick, Stuart; Bowlus, Christopher L.; Tanaka, Atsushi; Jones, David; Kremer, Andreas; Mayo, Marlyn J.; Haque, Nazneen; von Maltzahn, Robyn; Allinder, Matthew; Swift, Brandon; McLaughlin, Megan M.; et al. (Clinical Gastroenterology and Hepatology, 2023)
Background & Aims: GLIMMER assessed dose-response, efficacy, and safety of linerixibat, an ileal bile acid transporter inhibitor in development for cholestatic pruritus associated with primary biliary cholangitis (PBC). Methods: GLIMMER was a Phase 2b, multicenter, randomized, parallel-group study in adults with PBC and moderate-to-severe pruritus (≥4 on 0–10 numerical rating scale [NRS]). After 4 weeks of single-blind placebo, patients with NRS ≥3 were randomized (3:1) to double-blind linerixibat/placebo for 12 weeks (to week 16), followed by single-blind placebo (to week 20). The primary objective was to investigate dose-related changes in mean worst daily itch (MWDI) score. Results: One hundred forty-seven patients received placebo (n = 36) or linerixibat (once daily: 20 mg, n = 16; 90 mg, n = 23; 180 mg, n = 27; twice daily: 40 mg, n = 23; 90 mg, n = 22). Linerixibat groups exhibited ≥2-point mean reductions in MWDI from baseline at week 16; however, differences from placebo were not significant. Post hoc analysis of change from baseline in monthly itch score over the treatment period (Phase 3 endpoint) showed significant differences between placebo and linerixibat 180 mg once daily (P = .0424), 40 mg twice daily (P = .0105), and 90 mg twice daily (P = .0370). A significant relationship between total daily dose and response was observed post hoc in the per protocol population (P = .0542). Consistent with mechanism of action, diarrhea was the most frequent adverse event, and incidence increased with dose. Conclusions: Linerixibat effect on itch was not significantly different versus placebo in the primary intent-to-treat analysis but was associated with a significant dose-dependent reduction in itch in the per protocol population. A well-tolerated dose was identified for Phase 3 investigation for cholestatic pruritus in PBC. ClinicalTrials.gov ID: NCT02966834.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Bile Acids; Cholestatic Pruritus; Clinical Trial; IBAT Inhibitor; Patient-Reported Outcomes

Glucocorticoid-induced relapse of COVID-19 in a patient with sarcoidosis - Györfi, Andrea-Hermina; Kopp, Markus; May, Matthias; Vetter, Marcel; Uder, Michael; Kremer, Andreas; Schett, Georg; Harrer, Thomas; Distler, Jörg (Annals of the Rheumatic Diseases, 2020)
CRIS-Team Scopus Importer:2020-11-20

Glycochenodeoxycholate Promotes Liver Fibrosis in Mice with Hepatocellular Cholestasis - Hohenester, Simon; Kanitz, Veronika; Kremer, Andreas; Paulusma, Coen C.; Wimmer, Ralf; Kühn, Helen; Denk, Gerald; Horst, David; Elferink, Ronald Oude; Beuers, Ulrich (Cells, 2020)
Hydrophobic bile salts are considered to promote liver fibrosis in cholestasis. However, evidence for this widely accepted hypothesis remains scarce. In established animal models of cholestasis, e.g., by Mdr2 knockout, cholestasis and fibrosis are both secondary to biliary damage. Therefore, to test the specific contribution of accumulating bile salts to liver fibrosis in cholestatic disease, we applied the unique model of inducible hepatocellular cholestasis in cholate-fed Atp8b1(G308V/G308V) mice. Glycochenodeoxycholate (GCDCA) was supplemented to humanize the murine bile salt pool, as confirmed by HPLC. Biomarkers of cholestasis and liver fibrosis were quantified. Hepatic stellate cells (HSC) isolated from wild-type mice were stimulated with bile salts. Proliferation, cell accumulation, and collagen deposition of HSC were determined. In cholestatic Atp8b1(G308V/G308V) mice, increased hepatic expression of alpha SMA and collagen1a mRNA and excess hepatic collagen deposition indicated development of liver fibrosis only upon GCDCA supplementation. In vitro, numbers of myofibroblasts and deposition of collagen were increased after incubation with hydrophobic but not hydrophilic bile salts, and associated with EGFR and MEK1/2 activation. We concluded that chronic hepatocellular cholestasis alone, independently of biliary damage, induces liver fibrosis in mice in presence of the human bile salt GCDCA. Bile salts may have direct pro-fibrotic effects on HSC, putatively involving EGFR and MEK1/2 signaling.
CRIS-Team WoS Importer:2020-04-21

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

Hepatobiliary malignancy surveillance strategies in primary sclerosing cholangitis associate with reduced mortality - Bergquist, Annika M.; Weismueller, Tobias; Levy, Cynthia; Rupp, Christian; Joshi, Deepak; Nayagam, Jeremy; Montano-Loza, Aldo J.; Lytvyak, Ellina; Wunsch, Ewa; Milkiewicz, Piotr; Zenouzi, Roman; Schramm, Christoph; et al. (JOURNAL OF HEPATOLOGY, 2021)
CRIS-Team WoS Importer:2021-07-30

HLA-DO: a possible switch between GvHD and GvL effect - Zeun, J.; Neubeck, S.; Lang, Vanessa; Flamann, Cindy; Nagel, L.; Kunert, Timo; Vogler, T.; Brey, Stefanie; Hildner, Kai; Bäuerle, Tobias; Büttner-Herold, Maike; Winkler, Thomas; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

How Much Liver Tissue Is Required for Sufficient Histological Staging in Patients with Primary Biliary Cholangitis? - Vetter, Marcel; Kremer, Andreas; Agaimy, Abbas; Pfeifer, Lukas; Neurath, Markus; Zopf, Steffen; Siebler, Jürgen (Digestion, 2020)
Introduction: Histological alterations in primary biliary cholangitis (PBC) are heterogeneously distributed throughout the liver. Thus, the quality of histological staging is probably dependent on the available amount of liver tissue. The goals of this study were to test this hypothesis and to define biopsy conditions for obtaining sufficient tissue. Methods: In this retrospective analysis, we investigated 34 patient cases who fulfilled the criteria of the European Association for the Study of the Liver (EASL) for PBC and underwent a mini-laparoscopic liver biopsy between 2011 and 2018 using 16 or 18G needles. For histological assessment of fibrosis, we used the Ishak score, and the amount of tissue was measured by the number of portal fields. Histological staging was compared with the macroscopic mini-laparoscopic fibrosis score (MLFS), and non-invasive liver stiffness measurements using acoustic radiation force impulse (ARFI) imaging and the FIB-4 score. Results: Biopsy was successful in 33 of 34 patients (97%). Fibrosis assessment by MLFS and ARFI correlated strongly with each other (r = 0.7088, p = 0.000017). However, the correlation of both methods with the histological staging was weaker (MLFS vs. histology: r = 0.4231, p = 0.0142; ARFI vs. histology: r = 0.3564, p = 0.0577). The correlation of ARFI and MLFS with the histological staging was better in the subgroup of biopsies with at least 10 portal fields (= SG≥10PF) (MLFS vs. histology: r = 0.6369, p = 0.006; ARFI vs. histology: r = 0.7538, p = 0.0012). FIB-4 correlated weakly with the histological staging, which was statistically not significant (all samples: r = 0.2693, p = 0.1296; SG≥10PF: r = 0.2244, p = 0.3866). The number of portal fields correlated well with the length of the samples (r = 0.6436, p = 0.00012). The probability to attain at least 10 portal fields depended on the needle diameter and number of samples (1 × 16G or 18G [n = 10]: 30.0%; 2 × 18G [n = 15]: 53.3%; 2 × 16G [n = 5]: 100%; p = 0.0414). Conclusion: ARFI and MLFS are probably well suited for the assessment of liver fibrosis in patients with PBC. A minimum of 10 portal fields could improve the histological assessment in PBC and can probably be achieved by obtaining two 16G biopsies.
CRIS-Team Scopus Importer:2020-06-19

Human CD4+ T cells specific for dominant epitopes of SARS-CoV-2 Spike and Nucleocapsid proteins with therapeutic potential - Verhagen, Johan; van der Meijden, Edith; Lang, Vanessa; Kremer, Andreas; Völkl, Simon; Mackensen, Andreas; Aigner, Michael; Kremer, Anita (Clinical and Experimental Immunology, 2021)
Since December 2019, Coronavirus disease-19 (COVID-19) has spread rapidly throughout the world, leading to a global effort to develop vaccines and treatments. Despite extensive progress, there remains a need for treatments to bolster the immune responses in infected immunocompromised individuals, such as cancer patients who recently underwent a haematopoietic stem cell transplantation. Immunological protection against COVID-19 is mediated by both short-lived neutralizing antibodies and long-lasting virus-reactive T cells. Therefore, we propose that T cell therapy may augment efficacy of current treatments. For the greatest efficacy with minimal adverse effects, it is important that any cellular therapy is designed to be as specific and directed as possible. Here, we identify T cells from COVID-19 patients with a potentially protective response to two major antigens of the SARS-CoV-2 virus, Spike and Nucleocapsid protein. By generating clones of highly virus-reactive CD4+ T cells, we were able to confirm a set of nine immunodominant epitopes and characterize T cell responses against these. Accordingly, the sensitivity of T cell clones for their specific epitope, as well as the extent and focus of their cytokine response was examined. Moreover, using an advanced T cell receptor (TCR) sequencing approach, we determined the paired TCR-αβ sequences of clones of interest. While these data on a limited population require further expansion for universal application, the results presented here form a crucial first step towards TCR-transgenic CD4+ T cell therapy of COVID-19.
CRIS-Team Scopus Importer:2021-07-09
Keywords: COVID-19; epitope; SARS-CoV-2; T cell; T cell receptor

Identification of human CD4(+) T cells specific for dominant epitopes of SARS-CoV-2 Spike and Nucleocapsid proteins with therapeutic potential - Verhagen, Johan; van der Meijden, Edith; Lang, Vanessa; Kremer, Andreas; Völkl, Simon; Mackensen, Andreas; Aigner, Michael; Kremer, Anita (ONCOLOGY RESEARCH AND TREATMENT, 2021)
Since December 2019, Coronavirus disease-19 (COVID-19) has spread rapidly throughout the world, leading to a global effort to develop vaccines and treatments. Despite extensive progress, there remains a need for treatments to bolster the immune responses in infected immunocompromised individuals, such as cancer patients who recently underwent a haematopoietic stem cell transplantation. Immunological protection against COVID-19 is mediated by both short-lived neutralizing antibodies and long-lasting virus-reactive T cells. Therefore, we propose that T cell therapy may augment efficacy of current treatments. For the greatest efficacy with minimal adverse effects, it is important that any cellular therapy is designed to be as specific and directed as possible. Here, we identify T cells from COVID-19 patients with a potentially protective response to two major antigens of the SARS-CoV-2 virus, Spike and Nucleocapsid protein. By generating clones of highly virus-reactive CD4+ T cells, we were able to confirm a set of nine immunodominant epitopes and characterize T cell responses against these. Accordingly, the sensitivity of T cell clones for their specific epitope, as well as the extent and focus of their cytokine response was examined. Moreover, using an advanced T cell receptor (TCR) sequencing approach, we determined the paired TCR-αβ sequences of clones of interest. While these data on a limited population require further expansion for universal application, the results presented here form a crucial first step towards TCR-transgenic CD4+ T cell therapy of COVID-19.<br
CRIS-Team WoS Importer:2022-03-25
Keywords: COVID-19; SARS-CoV-2; T cell; T cell receptor; epitope

Identification of novel MRGX2-agonists triggering mast cell degranulation and potentially mediating drug-induced pruritus - Kühn, Helen; Wolf, Katharina; Boehm, F.; Glaudo, Markus; Gebhardt, Lisa; Ectors, Philipp; Agelopoulos, K.; Zahn, Dirk; Staender, S.; Kremer, Andreas (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

IgA2 Antibodies against SARS-CoV-2 Correlate with NET Formation and Fatal Outcome in Severely Diseased COVID-19 Patients - Staats, Leonie A. N.; Pfeiffer, Hella; Knopf, Jasmin; Lindemann, Aylin; Fürst, Julia; Kremer, Andreas; Hackstein, Holger; Neurath, Markus; Munoz, Luis Enrique; Achenbach, Susanne; Leppkes, Moritz; Herrmann, Martin; et al. (Cells, 2020)
Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) leads to an adaptive immune response in the host and the formation of anti-SARS-CoV-2 specific antibodies. While IgG responses against SARS-CoV-2 have been characterized quite well, less is known about IgA. IgA2 activates immune cells and induces inflammation and neutrophil extracellular trap (NET) formation which may contribute to organ injury and fatal outcome in SARS-CoV-2-infected patients. SARS-CoV-2 spike protein specific antibody levels were measured in plasma samples of 15 noninfected controls and 82 SARS-CoV-2-infected patients with no or mild symptoms, moderate symptoms (hospitalization) or severe disease (intensive care unit, ICU). Antibody levels were compared to levels of C-reactive protein (CRP) and circulating extracellular DNA (ecDNA) as markers for general inflammation and NET formation, respectively. While levels of SARS-CoV-2-specific IgG were similar in all patient groups, IgA2 antibodies were restricted to severe disease and showed the strongest discrimination between nonfatal and fatal outcome in patients with severe SARS-CoV-2 infection. While anti-SARS-CoV-2 IgG and IgA2 levels correlated with CRP levels in severely diseased patients, only anti-SARS-CoV-2 IgA2 correlated with ecDNA. These data suggest that the formation of anti-SARS-CoV-2 IgA2 during SARS-CoV-2 infection is a marker for more severe disease related to NET formation and poor outcome.
CRIS-Team WoS Importer:2021-01-15

Immune cell regulation by vitamin D-3 during allogeneic hematopoietic stem cell transplantation (HSCT) - Flamann, Cindy; Zeun, J.; Kremer, Andreas; Peter, K.; Kreutz, M.; Büttner-Herold, Maike; Kellner, C.; Saul, Domenica; Mougiakakos, Dimitrios; Mackensen, Andreas; Bruns, Heiko; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Impact of global Fxr deficiency on experimental acute pancreatitis and genetic variation in the FXR locus in human acute pancreatitis - Nijmeijer, Rian M.; Schaap, Frank G.; Smits, Alexander J. J.; Kremer, Andreas; Akkermans, Louis M. A.; Kroese, Alfons B. A.; Rijkers, Ger. T.; Schipper, Marguerite E. I.; Verheem, Andre; Wijmenga, Cisca; Gooszen, Hein G.; Van Erpecum, Karel J. (PLoS ONE, 2014)
Infectious complications often occur in acute pancreatitis, related to impaired intestinal barrier function, with prolonged disease course and even mortality as a result. The bile salt nuclear receptor farnesoid X receptor (FXR), which is expressed in the ileum, liver and other organs including the pancreas, exhibits anti-inflammatory effects by inhibiting NF-?B activation and is implicated in maintaining intestinal barrier integrity and preventing bacterial overgrowth and translocation. Here we explore, with the aid of complementary animal and human experiments, the potential role of FXR in acute pancreatitis.Experimental acute pancreatitis was induced using the CCK-analogue cerulein in wild-type and Fxr-/- mice. Severity of acute pancreatitis was assessed using histology and a semi-quantitative scoring system. Ileal permeability was analyzed in vitro by Ussing chambers and an in vivo permeability assay. Gene expression of Fxr and Fxr target genes was studied by quantitative RT-PCR. Serum FGF19 levels were determined by ELISA in acute pancreatitis patients and healthy volunteers. A genetic association study in 387 acute pancreatitis patients and 853 controls was performed using 9 tagging single nucleotide polymorphisms (SNPs) covering the complete FXR gene and two additional functional SNPs.In wild-type mice with acute pancreatitis, ileal transepithelial resistance was reduced and ileal mRNA expression of Fxr target genes Fgf15, SHP, and IBABP was decreased. Nevertheless, Fxr-/- mice did not exhibit a more severe acute pancreatitis than wild-type mice. In patients with acute pancreatitis, FGF19 levels were lower than in controls. However, there were no associations of FXR SNPs or haplotypes with susceptibility to acute pancreatitis, or its course, outcome or etiology.We found no evidence for a major role of FXR in acute human or murine pancreatitis. The observed altered Fxr activity during the course of disease may be a secondary phenomenon.
EVALuna2:1983

Impact on follow-up strategies in patients with primary sclerosing cholangitis - Bergquist, Annika; Weismueller, Tobias J.; Levy, Cynthia; Rupp, Christian; Joshi, Deepak; Nayagam, Jeremy Shanika; Montano-Loza, Aldo J.; Lytvyak, Ellina; Wunsch, Ewa; Milkiewicz, Piotr; Zenouzi, Roman; Schramm, Christoph; et al. (Liver International, 2022)
Background & Aims Evidence for the benefit of scheduled imaging for early detection of hepatobiliary malignancies in primary sclerosing cholangitis (PSC) is limited. We aimed to compare different follow-up strategies in PSC with the hypothesis that regular imaging improves survival. Methods We collected retrospective data from 2975 PSC patients from 27 centres. Patients were followed from the start of scheduled imaging or in case of clinical follow-up from 1 January 2000, until death or last clinical follow-up alive. The primary endpoint was all-cause mortality. Results A broad variety of different follow-up strategies were reported. All except one centre used regular imaging, ultrasound (US) and/or magnetic resonance imaging (MRI). Two centres used scheduled endoscopic retrograde cholangiopancreatography (ERCP) in addition to imaging for surveillance purposes. The overall HR (CI95%) for death, adjusted for sex, age and start year of follow-up, was 0.61 (0.47-0.80) for scheduled imaging with and without ERCP; 0.64 (0.48-0.86) for US/MRI and 0.53 (0.37-0.75) for follow-up strategies including scheduled ERCP. The lower risk of death remained for scheduled imaging with and without ERCP after adjustment for cholangiocarcinoma (CCA) or high-grade dysplasia as a time-dependent covariate, HR 0.57 (0.44-0.75). Hepatobiliary malignancy was diagnosed in 175 (5.9%) of the patients at 7.9 years of follow-up. Asymptomatic patients (25%) with CCA had better survival if scheduled imaging had been performed. Conclusions Follow-up strategies vary considerably across centres. Scheduled imaging was associated with improved survival. Multiple factors may contribute to this result including early tumour detection and increased endoscopic treatment of asymptomatic benign biliary strictures.
CRIS-Team WoS Importer:2022-06-03

Implementation of a national registry for patients with primary biliary cholangitis (PBC): The German PBC cohort - Wiegand, Johannes; Stein, Kerstin; Guenther, Rainer; Naumann, Uwe; Zimny, Sebastian; Reuken, Philipp; Boettler, Tobias; Bantel, Heike; Hofmann, Wolf Peter; Kremer, Andreas; Kautz, Achim; Beuers, Ulrich; et al. (JOURNAL OF HEPATOLOGY, 2021)
CRIS-Team WoS Importer:2021-07-30

Increased CD47 expression inhibits phagocytosis of alloreactive donor T cells after allo-HSCT - Flamann, Cindy; Matos, C.; Kreutz, M.; Shaikh, H.; Beilhack, A.; Büttner-Herold, Maike; Lischer, Christopher; Völkl, Simon; Kellner, C.; Zeun, J.; Kremer, Andreas; Bitterer, Katrin; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Influence of the autotaxin-lysophosphatidic acid axis on cellular function and cytokine expression in different breast cancer cell lines - Hauck, Theresa; Kadam, Sheetal; Heinz, Katharina; Garcia Peraza, Maria; Schmid, Rafael; Kremer, Andreas; Wolf, Katharina; Bauer, Alina; Horch, Raymund E.; Arkudas, Andreas; Kengelbach-Weigand, Annika (Scientific Reports, 2022)
Previous studies provide high evidence that autotaxin (ATX)-lysophosphatidic acid (LPA) signaling through LPA receptors (LPAR) plays an important role in breast cancer initiation, progression, and invasion. However, its specific role in different breast cancer cell lines remains to be fully elucidated to offer improvements in targeted therapies. Within this study, we analyzed in vitro the effect of LPA 18:1 and the LPAR1, LPAR3 (and LPAR2) inhibitor Ki16425 on cellular functions of different human breast cancer cell lines (MDA-MB-231, MDA-MB-468, MCF-7, BT-474, SKBR-3) and the human breast epithelial cell line MCF-10A, as well as Interleukin 8 (IL-8), Interleukin 6 (IL-6) and tumor necrosis factor (TNF)-alpha cytokine secretion after LPA-incubation. ATX-LPA signaling showed a dose-dependent stimulatory effect especially on cellular functions of triple-negative and luminal A breast cancer cell lines. Ki16425 inhibited the LPA-induced stimulation of triple-negative breast cancer and luminal A cell lines in variable intensity depending on the functional assay, indicating the interplay of different LPAR in those assays. IL-8, IL-6 and TNF-alpha secretion was induced by LPA in MDA-MB-468 cells. This study provides further evidence about the role of the ATX-LPA axis in different breast cancer cell lines and might contribute to identify subtypes suitable for a future targeted therapy of the ATX-LPA axis.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Cancer; Medical research; Molecular medicine

Integrin αVβ6: Autoantigen and Driver of Epithelial Remodeling in Colon and Bile Ducts in Primary Sclerosing Cholangitis and Inflammatory Bowel Disease. - Roth, Dominik; Düll, Miriam; Horst, Ludwig J.; Lindemann, Aylin; Malzer, Xenia; Koop, Kristina; Zundler, Sebastian; Vetter, Marcel; Jefremow, André; Atreya, Raja; Geppert, Carol-Immanuel; Weidemann, Sören; et al. (Journal of Crohns & Colitis, 2025)
BACKGROUND: Recently, autoantibodies directed against the epithelial adhesion protein integrin αVβ6 have been identified that are strongly associated with ulcerative colitis (UC). We aimed to elucidate whether anti-integrin αVβ6 (anti-αVβ6) is present in primary sclerosing cholangitis (PSC), its associated inflammatory bowel disease, or other cholestatic liver diseases and their persistence after proctocolectomy. METHODS: We detected anti-αVβ6 by an enzyme-linked immunosorbent assay in sera collected at 2 German tertiary centers, including healthy controls (N = 62), UC (N = 36), Crohn's disease (CD, N = 65), PSC-inflammatory bowel diseases (IBD) (78 samples from N = 41 patients), PSC without IBD (PSC, 41 samples from N = 18 patients), primary biliary cholangitis (PBC, N = 24), autoimmune hepatitis (AIH, N = 32), secondary sclerosing cholangitis (SSC, N = 12), and metabolic dysfunction-associated steatotic liver disease (MASLD, N = 24). In addition, sera after proctocolectomy were studied (44 samples/N = 10 patients). Immunofluorescent analyses were performed in tissue samples from liver, large bile duct from surgical resections, and colon of PSC patients. RESULTS: Anti-αVβ6 occurred in 91% of UC, 17% of CD, 73% of PSC-IBD, 39% of PSC, 4% of PBC, 14% of AIH, and 0% of healthy controls, SSC, or MASLD. Integrin αVβ6 is selectively expressed in disease-associated epithelia of both bile duct and colon. Anti-αVβ6 levels correlate moderately with intestinal disease activity in PSC-IBD, but only weakly with biliary disease. CONCLUSIONS: Anti-αVβ6 frequently occurs in patients suffering from PSC, especially in PSC-IBD. Anti-αVβ6 levels positively correlate to IBD activity in PSC-IBD, but may also occur in the absence of clinically manifest IBD in PSC.
EVALuna2:578869

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Bénard, Alan; Jacobsen, Anne; Brunner, Maximilian; Krautz, Christian; Klösch, Bettina; Swierzy, Izabela; Naschberger, Elisabeth; Podolska, Malgorzata; Kouhestani, Dina; David, Paul; Birkholz, Torsten; Castellanos, Ixchel; et al. (Nature Communications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-severe COVID-19 patients. In a mouse model of pulmonary HSV-1 infection, treatment with recombinant IL-3 reduces viral load and mortality. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating pDCs into the airways by stimulating CXCL12 secretion from pulmonary CD123+ epithelial cells, both, in mice and in COVID-19 negative patients exhibiting pulmonary diseases. This study identifies IL-3 as a predictive disease marker for SARS-CoV-2 infections and as a potential therapeutic target for pulmunory viral infections.
CRIS-Team Scopus Importer:2021-03-05

International experience of vedolizumab in primary sclerosis cholangitis and inflammatory bowel disease - Williamson, K.; Lytvyak, E.; Kremer, Andreas; De Krijger, M.; Trivedi, P.; Estes, D.; Yu, L.; Pratt, D.; De Vries, A.; Yimam, K. K.; Daretti, L.; Liu, C. H.; et al. (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

Intradermally applied LPA but not bile salts induce itch and pain in humans depending on the mode of application - Kremer, Andreas; Düll, Miriam; Wurm, L.; Ries, V.; Stengel, M.; Reeh, Peter; Fischer, Michael Jochen Marco; Namer, Barbara (2017)
EVALuna2:33355

Intrahepatic Cholestasis of Pregnancy - Jurk, Stanislaw M.; Kremer, Andreas; Schleussner, Ekkehard (Geburtshilfe und Frauenheilkunde, 2021)
Intrahepatic cholestasis of pregnancy (ICP) is a rare but potentially serious complication of pregnancy, the main symptom of which is intense pruritus with elevated serum levels of bile acids. The elevated serum bile acid concentration is regarded as a predictor for poor perinatal outcome including intrauterine death. Ursodeoxycholic acid (UDCA) has become established as the treatment of choice in clinical management to achieve a significant improvement in symptoms and reduce the cholestasis. Pregnant women with severe intrahepatic cholestasis should always be managed in a perinatal centre with close interdisciplinary monitoring and treatment involving perinatologists and hepatologists to minimise the markedly increased perinatal morbidity and mortality as well as maternal symptoms.
CRIS-Team WoS Importer:2021-09-03

Intrahepatic cholestasis of pregnancy : Rare but important - Kremer, Andreas; Wolf, Katharina; Staender, S. (Hautarzt, 2017)
Intrahepatic cholestasis of pregnancy (ICP) is a liver-specific disorder occurring in approximately 0.5-2.0% of all pregnancies with a considerable variation in certain ethnic groups. ICP usually runs a benign course for the mother and is characterized by maternal pruritus mainly in the third trimester, elevated transaminases and fasting total serum bile salts and increased fetal adverse events. The etiology of ICP is only partially understood but seems to be multifactorial. Cholestasis-inducing effects of certain female sex hormones and their metabolites play an important role in genetically susceptible women. The mechanisms resulting in fetal complications such as spontaneous preterm labour, antepartum passage of meconium, asphyxia events, still birth and fetal death are not well understood. Certain sulfated progesterone metabolites are likely to play a role in the pathogenesis of pruritus in ICP. In contrast to pregnancy-related dermatoses, pruritus does not present with primary skin alterations. However, intense scratching may cause secondary skin changes such as abrasions, excoriations and sometimes prurigo nodularis. Treatment is based on ursodeoxycholate treatment to reduce pruritus and hepatic impairment as well as elective delivery between gestation week 37-38 to pre-empt potential stillbirths. This article reviews clinical symptoms, diagnosis, treatment and in particular pathogenesis of pruritus in ICP.
EVALuna2:33922

Involvement of Neuro-Immune Interactions in Pruritus With Special Focus on Receptor Expressions - Ruppenstein, Aylin; Limberg, Maren M.; Loser, Karin; Kremer, Andreas; Homey, Bernhard; Raap, Ulrike (Frontiers in Medicine, 2021)
Pruritus is a common, but very challenging symptom with a wide diversity of underlying causes like dermatological, systemic, neurological and psychiatric diseases. In dermatology, pruritus is the most frequent symptom both in its acute and chronic form (over 6 weeks in duration). Treatment of chronic pruritus often remains challenging. Affected patients who suffer from moderate to severe pruritus have a significantly reduced quality of life. The underlying physiology of pruritus is very complex, involving a diverse network of components in the skin including resident cells such as keratinocytes and sensory neurons as well as transiently infiltrating cells such as certain immune cells. Previous research has established that there is a significant crosstalk among the stratum corneum, nerve fibers and various immune cells, such as keratinocytes, T cells, basophils, eosinophils and mast cells. In this regard, interactions between receptors on cutaneous and spinal neurons or on different immune cells play an important role in the processing of signals which are important for the transmission of pruritus. In this review, we discuss the role of various receptors involved in pruritus and inflammation, such as TRPV1 and TRPA1, IL-31RA and OSMR, TSLPR, PAR-2, NK1R, H1R and H4R, MRGPRs as well as TrkA, with a focus on interaction between nerve fibers and different immune cells. Emerging evidence shows that neuro-immune interactions play a pivotal role in mediating pruritus-associated inflammatory skin diseases such as atopic dermatitis, psoriasis or chronic spontaneous urticaria. Targeting these bidirectional neuro-immune interactions and the involved pruritus-specific receptors is likely to contribute to novel insights into the underlying pathogenesis and targeted treatment options of pruritus.
CRIS-Team Scopus Importer:2021-03-19
Keywords: atopic dermatitis (AD); chronic spontaneous urticaria (CSU); inflammation; neuro-immune; pruritus; psoriasis; sensory neurons; skin disease

Kniffelige Fälle – Wann bringt die Labordiagnostik eine Lösung? - Mettang, T.; Kremer, Andreas (Hautarzt, 2020)
Chronic pruritus is a symptom of many systemic diseases. In contrast to dermatological pruritus, there are no primary changes in skin appearance. Establishing the correct diagnosis in these cases can be quite challenging. In some instances, laboratory tests can be helpful. This report highlights the importance of specific and target-orientated laboratory tests in four patients with chronic pruritus due to systemic diseases.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Itch; Itching; Laboratory test; Pruritus; Systemic diseases

Lack of antibodies against seasonal coronavirus OC43 nucleocapsid protein identifies patients at risk of critical COVID-19 - Dugas, Martin; Grote-Westrick, Tanja; Merle, Uta; Fontenay, Michaela; Kremer, Andreas; Hanses, Frank; Vollenberg, Richard; Lorentzen, Eva; Tiwari-Heckler, Shilpa; Duchemin, Jérôme; Ellouze, Syrine; Vetter, Marcel; et al. (Journal of Clinical Virology, 2021)
Background: The vast majority of COVID-19 patients experience a mild disease. However, a minority suffers from critical disease with substantial morbidity and mortality. Objectives: To identify individuals at risk of critical COVID-19, the relevance of a seroreactivity against seasonal human coronaviruses was analyzed. Methods: We conducted a multi-center non-interventional study comprising 296 patients with confirmed SARS-CoV-2 infections from four tertiary care referral centers in Germany and France. The ICU group comprised more males, whereas the outpatient group contained a higher percentage of females. For each patient, the serum or plasma sample obtained closest after symptom onset was examined by immunoblot regarding IgG antibodies against the nucleocapsid protein (NP) of HCoV 229E, NL63, OC43 and HKU1. Results: Median age was 60 years (range 18-96). Patients with critical disease (n=106) had significantly lower levels of anti-HCoV OC43 nucleocapsid protein (NP)-specific antibodies compared to other COVID-19 inpatients (p=0.007). In multivariate analysis (adjusted for age, sex and BMI), OC43 negative inpatients had an increased risk of critical disease (adjusted odds ratio (AOR) 2.68 [95% CI 1.09 - 7.05]), higher than the risk by increased age or BMI, and lower than the risk by male sex. A risk stratification based on sex and OC43 serostatus was derived from this analysis. Conclusions: Our results suggest that prior infections with seasonal human coronaviruses can protect against a severe course of COVID-19. Therefore, anti-OC43 antibodies should be measured for COVID-19 inpatients and considered as part of the risk assessment for each patient. Hence, we expect individuals tested negative for anti-OC43 antibodies to particularly benefit from vaccination against SARS-CoV-2, especially with other risk factors prevailing.
CRIS-Team Scopus Importer:2021-05-21
Keywords: COVID-19; Critical disease; OC43; SARS-CoV-2; Seasonal coronavirus

LONG-TERM EFFICACY AND SAFETY OF OBETICHOLIC ACID IN PATIENTS WITH PBC FROM THE POISE TRIAL GROUPED BIOCHEMICALLY BY RISK OF DISEASE PROGRESSION - Bowlus, Christopher L.; Trauner, Michael H.; Kremer, Andreas; Liberman, Alexander; Malecha, Elizabeth Smoot; Macconell, Leigh; Nevens, Frederik (HEPATOLOGY, 2020)
CRIS-Team WoS Importer:2020-11-06

LONG-TERM EFFICACY AND SAFETY OF OBETICHOLIC ACID IN PRIMARY BILIARY CHOLANGITIS: RESPONDER ANALYSIS OF OVER 5 YEARS OF TREATMENT IN THE POISE TRIAL - Hansen, Bettina E.; Jones, David; Carbone, Marco; Bowlus, Christopher L.; Nevens, Frederik; Kremer, Andreas; Liberman, Alexander; Macconell, Leigh; Hirschfield, Gideon M. (HEPATOLOGY, 2020)
CRIS-Team WoS Importer:2020-11-06

Long-Term Obeticholic Acid (OCA) treatment associated with reversal or stabilization of fibrosis/cirrhosis in patients with Primary Biliary Cholangitis (PBC) - Bowlus, C.; Pockros, P.; Kremer, Andreas; Pares, A.; Forman, L.; Drenth, J. P.; Ryder, S.; Malecha, E. S.; Pencek, R.; Iloeje, U.; Macconell, L.; Shapiro, D.; et al. (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

Long-Term Obeticholic Acid Therapy Improves Histological Endpoints in Patients With Primary Biliary Cholangitis - Bowlus, Christopher L.; Pockros, Paul J.; Kremer, Andreas; Parés, Albert; Forman, Lisa M.; Drenth, Joost P.H.; Ryder, Stephen D.; Terracciano, Luigi; Jin, Yuying; Liberman, Alexander; Pencek, Richard; Iloeje, Uche; et al. (Clinical Gastroenterology and Hepatology, 2020)
Background & Aims: Primary biliary cholangitis (PBC) is an autoimmune disease characterized by bile duct destruction that can progress to cirrhosis. A liver biopsy substudy was conducted in the PBC obeticholic acid (OCA) International Study of Efficacy (POISE) to determine the long-term effects of OCA on liver damage and fibrosis in patients with PBC. POISE is a phase 3, double-blind, placebo-controlled, randomized trial with a 5-year open-label extension that evaluated 5 to 10 mg OCA daily in patients who were intolerant or unresponsive to ursodeoxycholic acid. Methods: Liver biopsy specimens were collected from 17 patients at time of enrollment in the double-blind phase and after 3 years of OCA treatment. Histologic evaluations were performed by 2 pathologists in a blinded, randomized fashion to determine the effects of OCA on fibrosis and other histologic parameters. Collagen morphometry assessments were performed by automated second harmonic generation and 2-photon excitation microscopy to observe quantitative measures of fibrosis. Results: From the time of enrollment until 3 years of treatment, most patients had improvements or stabilization in fibrosis (71%), bile duct loss (76%), ductopenia (82%), ductular reaction (82%), interface hepatitis (100%), and lobular hepatitis (94%). Over the 3-year period, we found significant reductions in collagen area ratio (median, –2.1; first quartile, –4.6, third quartile, –0.3; P =.013), collagen fiber density (median, –0.8; first quartile, –2.5; third quartile, 0; P =.021), collagen reticulation index (median, –0.1; first quartile, –0.3; third quartile, 0; P =.008), and fibrosis composite score (median, –1.0; first quartile, –2.5; third quartile, –0.5; P =.002). Conclusions: A subanalysis of data from the POISE study showed that long-term OCA treatment in patients with PBC is associated with improvements or stabilization of disease features, including ductular injury, fibrosis, and collagen morphometry features (ClinicalTrials.gov no: NCT01473524 and EudraCT no: 2011-004728-36).
CRIS-Team Scopus Importer:2020-03-27
Keywords: Farnesoid X Receptor Agonist; FXR Agonist; Hepatic; Liver Disease

Long-term obeticholic acid treatment is associated with improvements in collagen morphometry in patients with primary biliary cholangitis - Kremer, Andreas; Bowlus, Christopher; Bedossa, Pierre; Pares, Albert; Forman, Lisa; Drenth, Joost Ph; Ryder, Stephen; Terracciano, Luigi Maria; Jin, Yuying; Liberman, Alexander; Pencek, Richard; Macconell, Leigh; et al. (JOURNAL OF HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-05-07

Lysophosphatidic acid activates nociceptors and causes pain or itch depending on the application mode in human skin - Düll, Miriam; Stengel, Martina; Ries, Vivien; Strupf, Marion; Reeh, Peter; Kremer, Andreas; Namer, Barbara (Pain, 2022)
ABSTRACT: Lysophosphatidic acid (LPA) is involved in the pathophysiology of cholestatic pruritus and neuropathic pain. Slowly conducting peripheral afferent C-nerve fibers are crucial in the sensations of itch and pain. In animal studies, specialized neurons ("pruriceptors") have been described, expressing specific receptors, eg, from the Mas-related G-protein-coupled receptor family. Human nerve fibers involved in pain signaling ("nociceptors") can elicit itch if activated by focalized stimuli such as cowhage spicules. In this study, we scrutinized the effects of LPA in humans by 2 different application modes on the level of psychophysics and single nerve fiber recordings (microneurography). In healthy human subjects, intracutaneous LPA microinjections elicited burning pain, whereas LPA application through inactivated cowhage spicules evoked a moderate itch sensation. Lysophosphatidic acid microinjections induced heat hyperalgesia and hypersensitivity to higher electrical stimulus frequencies. Pharmacological blockade of transient receptor potential channel A1 or transient receptor potential channel vanilloid 1 reduced heat hyperalgesia, but not acute chemical pain. Microneurography revealed an application mode-dependent differential activation of mechanosensitive (CM) and mechanoinsensitive C (CMi) fibers. Lysophosphatidic acid microinjections activated a greater proportion of CMi fibers and more strongly than CM fibers; spicule application of LPA activated CM and CMi fibers to a similar extent but excited CM fibers more and CMi fibers less intensely than microinjections. In conclusion, we show for the first time in humans that LPA can cause pain as well as itch dependent on the mode of application and activates afferent human C fibers. Itch may arise from focal activation of few nerve fibers with distinct spatial contrast to unexcited surrounding afferents and a specific combination of activated fiber subclasses might contribute.
CRIS-Team Scopus Importer:2022-02-25

Lysophosphatidic acid activates peripheral glia cells via LPA receptor 1 - Wolf, Katharina; Gebhardt, L.; Robering, J.; Fischer, M.; Kremer, Andreas (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

Lysophosphatidic acid activates peripheral glial cells - Gebhardt, Lisa; Robering, J; Ciotu, C.; Wolf, Katharina; Kühn, Helen; Kremer, Andreas; Fischer, M. (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Lysophosphatidic acid activates satellite glia cells and Schwann cells - Robering, Jan Willem; Gebhardt, Lisa; Wolf, Katharina; Kühn, Helen; Kremer, Andreas; Fischer, Michael Jochen Marco (Glia, 2019)
Pruritus is a common and disabling symptom in patients with hepatobiliary disorders, particularly in those with cholestatic features. Serum levels of lysophosphatidic acid (LPA) and its forming enzyme autotaxin were increased in patients suffering from hepatic pruritus, correlated with itch severity and response to treatment. Here we show that in a culture of dorsal root ganglia LPA 18:1 surprisingly activated a large fraction of satellite glia cells, and responses to LPA 18:1 correlated inversely with responses to neuronal expressed transient receptor potential channels. LPA 18:1 caused only a marginal activation of heterologously expressed TRPV1, and responses in dorsal root ganglion cultures from TRPV1-deficient mice were similar to controls. LPA 18:1 desensitized subsequent responsiveness to chloroquine and TGR5 agonist INT-777. The LPA 18:1-induced increase in cytoplasmatic calcium stems from the endoplasmatic reticulum. LPA receptor expression in dorsal root ganglia and Schwann cells, LPAR1 immunohistochemistry, and pharmacological results indicate a signaling pathway through LPA receptor 1. Peripheral rat Schwann cells, which are of glial lineage as the satellite glia cells, were also responsive to LPA 18:1. Summarizing, LPA 18:1 primarily activates rather glial cells than neurons, which may subsequently modulate neuronal responsiveness and sensory sensations such as itch and pain.
CRIS-Team WoS Importer:2019-04-04

LYSOPHOSPHATIDIC ACID INDUCES ITCH AND PAIN IN HUMANS DEPENDING ON THE MODE OF APPLICATION - Düll, Miriam; Wurm, Lina; Ries, Vivien; Stengel, Martina; Reeh, Peter; Fischer, Michael J.; Namer, Barbara; Kremer, Andreas (2017)
EVALuna2:33336

Management of Chronic Hepatic Itch - Düll, Miriam; Kremer, Andreas (Dermatologic Clinics, 2018)
Hepatic itch remains among the most agonizing symptoms for affected patients and a major clinical challenge for physicians. Pruritus may occur in almost all liver diseases, particularly those with cholestatic features. Hepatic itch arises irrespective of the severity of the underlying liver disease or extent of cholestasis. Antihistamines are ineffective in hepatic itch. Therapeutic recommendations consist of a guideline-based stepwise approach, starting with the anion exchange resin cholestyramine, followed by rifampicin, naltrexone, and sertraline. Bezafibrate and ileal bile acid transporter inhibitors are promising future treatment options. Experimental and invasive procedures should be reserved for refractory pruritus.
EVALuna2:35154

Management of pruritus in patients with cholestatic liver disease - Kremer, Andreas; Kraus, M. R. (MMW Fortschritte der Medizin, 2016)
EVALuna2:2221

Mas-related G protein–coupled receptor X2 and its activators in dermatologic allergies - Kühn, Helen; Kolkhir, Pavel; Babina, Magda; Düll, Miriam; Frischbutter, Stefan; Fok, Jie Shen; Jiao, Qingqing; Metz, Martin; Scheffel, Jörg; Wolf, Katharina; Kremer, Andreas; Maurer, Marcus (Journal of Allergy and Clinical Immunology, 2020)
The Mas-related G protein–coupled receptor X2 (MRGPRX2) is a multiligand receptor responding to various exogenous and endogenous stimuli. Being highly expressed on skin mast cells, MRGPRX2 triggers their degranulation and release of proinflammatory mediators, and it promotes multicellular signaling cascades, such as itch induction and transmission in sensory neurons. The expression of MRGPRX2 by skin mast cells and the levels of the MRGPRX2 agonists (eg, substance P, major basic protein, eosinophil peroxidase) are upregulated in the serum and/or skin of patients with inflammatory and pruritic skin diseases, such as chronic spontaneous urticaria or atopic dermatitis. Therefore, MRGPRX2 and its agonists might be potential biomarkers for the progression of cutaneous inflammatory diseases and the response to treatment. In addition, they may represent promising targets for prevention and treatment of signs and symptoms in patients with skin diseases or drug reactions. To assess this possibility, this review explores the role and relevance of MRGPRX2 and its activators in cutaneous inflammatory disorders and chronic pruritus.
CRIS-Team Scopus Importer:2020-10-23
Keywords: agonists; antimicrobial peptides; atopic dermatitis; chronic spontaneous urticaria; eosinophil granule proteins; itch; MRGPRX2; MRGX2; neuropeptides; pruritus; substance P

Modulation of the extrinsic cell death signaling pathway by viral Flip induces acute-death mediated liver failure - Bittel, Miriam; Kremer, Andreas; Stürzl, Michael; Wirtz, Stefan; Stolzer, Iris; Neurath, Markus; Ballon, Gianna; Günther, Claudia (Cell Death & Disease, 2019)
During viral infections viruses express molecules that interfere with the host-cell death machinery and thus inhibit cell death responses. For example the viral FLIP (vFLIP) encoded by Kaposi’s sarcoma-associated herpesvirus interacts and inhibits the central cell death effector, Caspase-8. In order to analyze the impact of anti-apoptotic viral proteins, like vFlip, on liver physiology in vivo, mice expressing vFlip constitutively in hepatocytes (vFlipAlbCre+) were generated. Transgenic expression of vFlip caused severe liver tissue injury accompanied by massive hepatocellular necrosis and inflammation that finally culminated in early postnatal death of mice. On a molecular level, hepatocellular death was mediated by RIPK1-MLKL necroptosis driven by an autocrine TNF production. The loss of hepatocytes was accompanied by impaired bile acid production and disruption of the bile duct structure with impact on the liver-gut axis. Notably, embryonic development and tissue homeostasis were unaffected by vFlip expression. In summary our data uncovered that transgenic expression of vFlip can cause severe liver injury in mice, culminating in multiple organ insufficiency and death. These results demonstrate that viral cell death regulatory molecules exhibit different facets of activities beyond the inhibition of cell death that may merit more sophisticated in vitro and in vivo analysis.
CRIS-Team Scopus Importer:2019-12-03

Molecular cross-talk between Y5-receptor and neuropeptide Y drives liver cancer - Dietrich, Peter; Wormser, Laura; Fritz, Valerie; Seitz, Tatjana; de Maria, Monica; Schambony, Alexandra; Kremer, Andreas; Günther, Claudia; Itzel, Timo; Thasler, Wolfgang E.; Teufel, Andreas; Trebicka, Jonel; et al. (Journal of Clinical Investigation, 2020)
Hepatocellular carcinoma (HCC) is clearly age-related and represents one of the deadliest cancer types worldwide. Due to globally increasing risk factors including metabolic disorders, the incidence rates of HCC are still rising. However, the molecular hallmarks of HCC remain poorly understood. Neuropeptide Y (NPY) and NPY-receptors represent a highly conserved, stress-activated system which is involved in diverse cancer-related hallmarks including aging and metabolic alterations, but its impact on liver cancer had been unclear. Here, we observed increased NPY5-receptor (Y5R) expression in HCC which correlated with tumor growth and survival. Furthermore, we found that its ligand NPY was secreted by peri-tumorous hepatocytes. Hepatocyte-derived NPY promoted HCC progression by Y5R-activation. Transforming growth factor beta 1 (TGFβ1) was identified as a regulator of NPY in hepatocytes and induced Y5R in invasive cancer cells. Moreover, NPY-conversion by dipeptidylpeptidase 4 (DPP4) augmented Y5R-activation and function in liver cancer. The TGFβ-NPY-Y5R-axis and DPP4 represent attractive therapeutic targets for controlling liver cancer progression.
EVALuna2:212290
Keywords: Aging; Cancer; Hepatology

MRGPRX2 ligandome: Molecular simulations reveal three categories of ligand-receptor interactions - Maier, Philip; Macht, Moritz; Beck, Silvan; Kolkhir, Pavel; Babina, Magda; Kremer, Andreas; Zahn, Dirk; Wolf, Katharina (Journal of Structural Biology, 2025)
Introduction: Mas-related G protein-coupled receptor (MRGPR) X2 is a mast cell receptor known to be activated by a wide range of ligands of various size, charge and origin. Our aim is to gain a deeper understanding of the binding processes of the different MRGPRX2 ligands and the ligand-receptor interactions in order to identify crucial structural elements for receptor activation. Materials and methods: We used the three-dimensional structure of MRGPRX2 described in Nature in 2021 by Cao et al. and Yang et al. to computationally model the interaction between MRGPRX2 and small molecule ligands under simulated physiological conditions. Results: Docking and post-docking samplings of the MRGPRX2 ligandome within the GPCR binding pocket led to the identification of key structural features for protein–ligand interactions. On the ligand side, we obtained an overlay of different molecular patterns or chemical groups by comparing different ligands plotted on the receptor. These key features include at least one protonated amine moiety of MRGPRX2 ligands contributing to one salt-bridge and one π-cation interaction, as well as an extended non-polar domain of the ligand surface that offer hydrophobic segregation and/or π-stacking interactions. In the receptor, we identified amino acids (GLU164, ASP184, PHE101, PHE170, TRP243, PHE244 and PHE257) that specifically interact via hydrogen bonding, salt-bridges, π-cation interactions and π-π stacking with the ligands to direct binding and ultimately receptor activation. Discussion: Our insights into ligand-receptor interaction obtained by molecular modeling can help to predict mast cell activation via MRGPRX2 including adverse reactions, and facilitate the development of MRGPRX2 antagonists for the treatment of mast cell-mediated diseases.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Docking; Ligand-receptor interaction; Mas-related G protein coupled receptor X2; Molecular recognition; Pharmacophore

Newer Approaches to the Management of Pruritus in Cholestatic Liver Disease - Düll, Miriam; Kremer, Andreas (Current Hepatology Reports, 2020)
Purpose of Review: Chronic pruritus represents a burdensome symptom in cholestatic liver disease. This review recommends a stepwise therapeutic approach, alongside with providing information on epidemiology, pathophysiology, and novel drug targets. Recent Findings: Current epidemiological data emphasize chronic itch as a major symptom in immune-mediated liver diseases such as primary biliary cholangitis affecting up to 70% of patients with a significant number suffering from long-lasting and severe pruritus. κ-opioid receptor (KOR) agonists, PPAR agonists, and ileal bile acid transporter (IBAT) inhibitors are currently investigated for their anti-pruritic efficacy in clinical trials. Future therapies may target the autotaxin-lysophosphatidic acid-axis or the Mas-related GPCR MRGPRX4. Summary: Cholestatic pruritus still remains a challenging symptom for patients and physicians. Using a stepwise approach including cholestyramine, rifampicin, bezafibrate, naltrexone, and sertraline, pruritus is often adequately manageable. KOR agonists and IBAT inhibitors are currently the most promising anti-pruritic drugs for cholestatic pruritus in development.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Autotaxin; Bezafibrate; Bile salt; IBAT; Itch; Opioid; Rifampicin

New findings regarding the neurobiology of pruritus - Pereira, M. P.; Agelopoulos, K.; Kremer, Andreas; Schmelz, M. (Hautarzt, 2018)
Chronic pruritus may arise from different conditions, including dermatological, systemic, neurologic, psychiatric, and psychosomatic diseases, leading to a substantial decrease in the quality of life of affected patients. The neurobiological mechanisms involved in chronic pruritus are not yet fully understood. However, in recent years important achievements have been made in this regard. This article aims to provide an overview of the current understanding of these mechanisms. The complex network of neurons, keratinocytes, inflammatory cells, cytokines, and neurotrophic factors which play a role in the development and maintenance of chronic pruritus are highlighted, as well as the pruritogens involved in pruritic diseases in humans. Additionally, the importance of neuropathy and scratch-induced changes for the pathophysiology of chronic pruritus are discussed. The new findings on the neurobiological mechanisms underlying chronic pruritus have already led to the development of novel therapies, e. g., monoclonal antibodies against specific interleukins, which are important for pruritus transmission. A deeper understanding of the neurobiological mechanisms is necessary in order to develop specifically targeted therapeutic options and thus provide better care for affected patients.
EVALuna2:35152

Non-dermatological challenges of chronic itch - Kremer, Andreas; Mettang, Thomas; Weisshaar, Elke (Acta Dermato-Venereologica, 2020)
Chronic itch occurs in many skin diseases, but also in a variety of systemic, neurological, and psychogenic/ psychosomatic disorders, or is caused by drug intake. When several diseases or causes co-exist, chronic itch is categorized as “mixed origin”. These patients present with unaltered skin or with chronic scratch lesions including chronic prurigo. Precise diagnostics are necessary to evaluate the underlying aetiology, to enable identification of the best treatment available, and to improve patients’ quality of life. This is of particular relevance in elderly people in whom chronic itch is often of systemic or mixed origin. Xerosis cutis is a frequent cofactor contributing to chronic itch of non-dermatological origin. Treatment is frequently multi-modal, considering age, comorbidities, current drug intake, quality and intensity of itch. With regard to the demographic situation of the population, characterized by increasing life expectancy and polypharmacy, itch of non-dermatological origin will represent an increasing medical challenge in the future.
CRIS-Team Scopus Importer:2020-01-24
Keywords: Cholestasis; Chronic kidney disease; Liver; Pruritus; Systemic disease; Uraemic itch

norUrsodeoxycholic acid (norUDCA) improves non-alcoholic fatty liver disease (NAFLD): Results from a randomized placebo-controlled, double-blind phase IIa study - Traussnigg, Stefan; Schattenberg, Jorn M.; Demir, Muenevver; Wiegand, Johannes; Geier, Andreas; Teuber, Gerlinde; Hofmann, Wolf Peter; Kremer, Andreas; Spreda, Frank; Kluwe, Johannes; Petersen, Joerg; Boettler, Tobias; et al. (2017)
EVALuna2:33892

Norursodeoxycholic acid versus placebo in the treatment of non-alcoholic fatty liver disease: a double-blind, randomised, placebo-controlled, phase 2 dose-finding trial - Traussnigg, Stefan; Schattenberg, Jörn M.; Demir, Münevver; Wiegand, Johannes; Geier, Andreas; Teuber, Gerlinde; Hofmann, Wolf Peter; Kremer, Andreas; Spreda, Frank; Kluwe, Johannes; Petersen, Jörg; Boettler, Tobias; et al. (Lancet Gastroenterology and Hepatology, 2019)
Background: Norursodeoxycholic acid is an orally administered side chain-shortened homologue of ursodeoxycholic acid that undergoes hepatic enrichment with hepatoprotective, anti-inflammatory, and antifibrotic activity. We assessed the efficacy of two doses of norursodeoxycholic acid versus placebo for the treatment of non-alcoholic fatty liver disease. Methods: We did a multicentre, double-blind, placebo-controlled, randomised, phase 2 dose-finding clinical trial in tertiary referral hospitals and medical centres in Austria (n=6) and Germany (n=23) for patients with non-alcoholic fatty liver disease with or without diabetes. Patients with a clinical diagnosis of non-alcoholic fatty liver disease and serum alanine aminotransferase (ALT) concentrations of more than 0·8 times the upper limit of normal were randomly assigned (1:1:1) using a computer-generated central randomisation. Patients were randomly assigned to receive either norursodeoxycholic acid capsules at 500 mg per day or 1500 mg per day, or placebo, for 12 weeks with a subsequent 4-week follow-up period. All individuals involved in the trial were masked to treatment allocation. The primary efficacy endpoint was the mean relative percentage change in ALT concentrations between baseline and end of treatment assessed in the intention-to-treat population. This trial is registered with EudraCT, number 2013-004605-38. Findings: Between March 30, 2015, and Sept 20, 2016, of 198 individuals included in the analysis, 67 patients were randomly assigned to receive 500 mg norursodeoxycholic acid, 67 to 1500 mg norursodeoxycholic acid, and 64 to placebo. A dose-dependent reduction in serum ALT between baseline and end of treatment was observed with norursodeoxycholic acid versus placebo, with a significant effect in the 1500 mg group (mean change −27·8%, 95% repeated CI −34·7 to −14·4; p<0·0001). Serious adverse events (n=6) and treatment-emergent adverse events (n=314) were reported in a similar proportion of patients across groups. 112 treatment-emergent adverse events occurred in the 1500 mg group, 99 in the 500 mg group, and 103 in the placebo group. The most frequent adverse events were headache, gastrointestinal disorders, and infections (eg, diarrhoea, abdominal pain, or nasopharyngitis). Interpretation: Norursodeoxycholic acid at 1500 mg resulted in a significant reduction of serum ALT within 12 weeks of treatment when compared with placebo. Norursodeoxycholic acid was safe and well tolerated encouraging further studies. Funding: Dr Falk Pharma GmbH.
CRIS-Team Scopus Importer:2019-08-02

OBETICHOLIC ACID TREATMENT IS ASSOCIATED WITH IMPROVED COLLAGEN MORPHOMETRY IN PATIENTS WITH PRIMARY BILIARY CHOLANGITIS - Kremer, Andreas; Bowlus, Christopher L.; Bedossa, Pierre; Pares, Albert; Forman, Lisa M.; Drenth, Joost P. H.; Ryder, Stephen; Terracciano, Luigi; Jin, Yuying; Liberman, Alexander; Pencek, Richard; Macconell, Leigh; et al. (GUT, 2019)
CRIS-Team WoS Importer:2020-04-14

OMW: Diagnostik bei Pruritus auf primär unveränderter Haut - Düll, Miriam; Kremer, Andreas (Die Dermatologie, 2024)
CRIS-Team Scopus Importer:2024-10-11

Pathogenesis and Management of Pruritus in PBC and PSC - Kremer, Andreas; Namer, Barbara; Bolier, Ruth; Fischer, Michael; Elferink, Ronald P. Oude; Beuers, Ulrich (Digestive Diseases, 2015)
Pruritus is a preeminent symptom in patients with chronic cholestatic liver disorders such as primary biliary cirrhosis and primary sclerosing cholangitis. More than two-thirds of these patients experience itching during the course of their disease. This symptom is also frequently observed in patients with other causes of cholestasis such as cholangiocarcinoma, inherited forms of cholestasis and intrahepatic cholestasis of pregnancy, but may accompany almost any other liver disease. The pathogenesis of pruritus of cholestasis remains largely elusive. Increased concentrations of bile salts, histamine, serotonin, progesterone metabolites and endogenous opioids have been controversially discussed as potential pruritogens. However, for these molecules, neither a correlation with itch intensity nor a causative link could be established. The G protein-coupled receptor for bile salts, TGR5, has been shown to be expressed in dorsal root ganglia and give rise to itch in rodents, albeit upon stimuli with suprapathological concentrations of bile salts. The potent neuronal activator lysophosphatidic acid (LPA) and its forming enzyme, autotaxin (ATX), could be identified in the serum of patients with cholestatic pruritus. ATX activity correlated with itch severity and effectiveness of several anti-pruritic therapeutic interventions in cholestatic patients. Thus, the ATX-LPA-axis may represent a key element in the pathogenesis of this agonizing symptom. Treatment options for pruritus of cholestasis remain limited to a few evidence-based and several experimental medical and interventional therapies. The current guideline-based recommendations include the anion exchange resins colestyramine, the pregnane X receptor-agonist and enzyme inducer rifampicin, the ?-opioid antagonist naltrexone, and the selective serotonin reuptake inhibitors sertraline. Still, a considerable part of patients is unresponsive to these drugs and requires experimental approaches including phototherapy, plasmapheresis, albumin dialysis or nasobiliary drainage. This review outlines the current knowledge on pathogenesis of cholestatic pruritus and summarizes evidence-based and experimental therapeutic interventions for cholestatic patients with itch.
EVALuna2:1849

Patients Receiving Cytokine Inhibitors Have Low Prevalence of SARS-CoV-2 Infection - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

Pearls & Oy-sters: SARS-CoV-2 Infection of the CNS in a Patient With Meningeosis Carcinomatosa - Steininger, Philipp; Seifert, Frank; Balk, Stefanie; Kuramatsu, Joji; Kremer, Andreas; Coras, Roland; Engelhorn, Tobias; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Enßer, Armin (Neurology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Peripheral Sensitization and Loss of Descending Inhibition Is a Hallmark of Chronic Pruritus - Pogatzki-Zahn, Esther M.; Pereira, Manuel P.; Cremer, Alexander; Zeidler, Claudia; Dreyer, Tim; Riepe, Claudia; Wempe, Carola; Lotts, Tobias; Segelcke, Daniel; Ringkamp, Matthias; Kremer, Andreas; Agelopoulos, Konstantin; et al. (Journal of Investigative Dermatology, 2019)
Neurophysiological mechanisms leading to chronicity of pruritus are not yet fully understood and it is not known whether these mechanisms diverge between different underlying diseases of chronic pruritus (CP). This study aimed to detect such mechanisms in CP of various origins. A total of 120 patients with CP of inflammatory origin (atopic dermatitis), neuropathic origin (brachioradial pruritus), and chronic prurigo of nodular type, the latter as a model for chronic scratching, as well as 40 matched healthy controls participated in this study. Stimulation with cowhage induced a more intensive itch sensation compared with stimulation with other substances in all patient groups but not in healthy controls, arguing for sensitization of cutaneous mechano- and heat-sensitive C-fibers in CP. All patient groups showed a decreased intraepidermal nerve fiber density compared with controls. A decreased condition pain modulation effect was observed in all patient groups compared with controls, suggesting a reduced descending inhibitory system in CP. In sum, CP of different etiologies showed a mixed peripheral and central pattern of neuronal alterations, which might contribute to the chronicity of pruritus with no differences between pruritus entities. Our findings may contribute to the development of future treatment strategies targeting these pathomechanisms.
CRIS-Team Scopus Importer:2019-09-17

PGAM5-mediated programmed necrosis of hepatocytes drives acute liver injury - He, Gui-Wei; Günther, Claudia; Kremer, Andreas; Thonn, Veronika; Amann, Kerstin Ute; Poremba, Christopher; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Gut, 2016)
Autoimmune hepatitis (AIH) is a severe necroinflammatory liver disease associated with significant mortality. Although loss of hepatocytes is generally recognised as a key trigger of liver inflammation and liver failure, the regulation of hepatic cell death causing AIH remains poorly understood. The aim of this study was to identify molecular mechanisms that drive hepatocyte cell death in the pathogenesis of acute liver injury.Acute liver injury was modelled in mice by intravenous administration of concanavalin A (ConA). Liver injury was demonstrated by serum transaminases and histological assessment of liver sections. PGAM5-deficient mice (PGAM5-/-) were used to determine its role in experimental hepatitis. Mdivi-1 was used as an inhibitor of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Mitochondrial fission and the expression of PGAM5 were compared between liver biopsies derived from patients with AIH and control patients.PGAM5 was highly expressed in hepatocytes of patients with AIH and in mice with ConA-induced experimental hepatitis. Deficiency of PGAM5 protected mice from ConA-induced hepatocellular death and liver injury. PGAM5 regulated ConA-induced mitochondrial fission in hepatocytes. Administration of the Drp1-inhibitor Mdivi-1 blocked mitochondrial fission, diminished hepatocyte cell death and attenuated liver tissue damage induced by ConA.Our data demonstrate for the first time that PGAM5 plays an indispensable role in the pathogenesis of ConA-induced liver injury. Downstream of PGAM5, Drp1-mediated mitochondrial fission is an obligatory step that drives the execution of hepatic necrosis and tissue damage. Our data highlight the PGAM5-Drp1 axis as a potential therapeutic target for acute immune-mediated liver injury.
EVALuna2:2219

Primary biliary cholangitis-established and novel therapies - Vetter, Marcel; Kremer, Andreas (Internist, 2018)
BACKGROUND: Patients with primary biliary cholangitis (PBC, formerly primary biliary cirrhosis) and insufficient treatment response or risk factors exhibit a remarkably increased risk for disease progression and associated complications. Furthermore, extrahepatic manifestations may considerably reduce quality of life in affected patients. OBJECTIVES: This article presents an overview on standard therapy with ursodeoxycholic acid (UDCA) and further therapeutic options in patients with insufficient treatment response. In addition, symptom-orientated therapies will be presented in a practical and compact way. METHODS: The current European and German guidelines from 2017 in addition to several research papers and expert opinions are the basis for this review. RESULTS: Every PBC patient should be treated with UDCA life-long. In case of insufficient response to UDCA, obeticholic acid (OCA) has been approved as second line therapy since 2016. Fibrates and budesonide present off-label options for certain patient subpopulations. Pruritus should initially be treated with colestyramine. In case of insufficient efficacy or intolerance, rifampicin represents the most effective off-label option. If fatigue is present, differential diagnoses shall be excluded and coping strategies combined with regular physical activity can have a positive effect. CONCLUSION: UDCA and OCA are effective and approved drugs for treating PBC. Patients with insufficient treatment response or risk factors have to be treated consequently. Due to the improved anti-cholestatic treatment options, therapies to reduce fatigue and pruritus are increasingly important.
EVALuna2:35165

Prognostic and mechanistic potential of progesterone sulfates in intrahepatic cholestasis of pregnancy and pruritus gravidarum - Abu-Hayyeh, Shadi; Ovadia, Caroline; Lieu, Tinamarie; Jensen, Dane D.; Chambers, Jenny; Dixon, Peter H.; Lövgren-Sandblom, Anita; Bolier, Ruth; Tolenaars, Dagmar; Kremer, Andreas; Syngelaki, Argyro; Noori, Muna; et al. (Hepatology, 2015)
A challenge in obstetrics is to distinguish pathological symptoms from those associated with normal changes of pregnancy, typified by the need to differentiate whether gestational pruritus of the skin is an early symptom of intrahepatic cholestasis of pregnancy (ICP), or due to benign pruritus gravidarum (PG). ICP is characterised by raised serum bile acids, and complicated by spontaneous preterm labour and stillbirth. A biomarker for ICP would be invaluable for the early diagnosis and treatment and to enable its differentiation from other maternal diseases. Three progesterone sulfate compounds, whose concentrations have not previously been studied, were newly synthesized and assayed in the serum of three groups of ICP patients and found to be significantly higher in ICP at 9-15 weeks of gestation and prior to symptom onset (group 1 cases/samples: ICP n=35/80, uncomplicated pregnancy=29/100), demonstrating that all three progesterone sulfates are prognostic for ICP. Concentrations of progesterone sulfates were associated with itch severity and, in combination with autotaxin, distinguished pregnant women with itch that would subsequently develop ICP from PG (group 2: ICP n=41, PG n=14). In a third group of first trimester samples all progesterone sulfates were significantly elevated in serum from low-risk asymptomatic women who subsequently developed ICP (ICP/uncomplicated pregnancy n=54/51). Finally, we show mechanistically that progesterone sulfates mediate itch by evoking a Tgr5-dependent scratch response in mice.Our discovery that sulfated progesterone metabolites are a prognostic indicator for ICP will help predict onset of ICP and distinguish it from benign pruritus gravidarum, enabling targeted obstetric care to a high risk population. Delineation of a progesterone sulfate-TGR5 pruritus axis identifies a therapeutic target for itch management in ICP. This article is protected by copyright. All rights reserved.
EVALuna2:2027

Pruritus bei systemischen Erkrankungen - Kremer, Andreas; Mettang, T. (Internist, 2019)
Chronic pruritus is a symptom of various internal disorders. In contrast to dermatological diseases, pruritus does not present with primary skin alterations in these patients. However, intense scratching my cause secondary skin changes such as abrasion, excoriation, prurigo nodularis, or in rare cases even scarring. The most common internal causes for chronic pruritus are chronic kidney disease, hepatobiliary, and hematological disorders as well as adverse drug reactions. Pruritus is less commonly seen in patients with endocrine or metabolic diseases, malabsorption syndromes, infectious diseases, and solid tumors. The pathogenesis of pruritus in these disorders remains largely elusive, albeit first insights have been gained for uremic and cholestatic pruritus. Antipruritic treatment is therefore symptomatic in most cases and may represent a clinical challenge. The calcium channel blockers gabapentin and pregabalin have the best proven efficacy in chronic kidney disease associated pruritus. In Japan, nalfurafine, a κ-opioid receptor agonist, has been licensed for this indication. UVB light may also attenuate uremic symptoms. In patients suffering from hepatobiliary disorders the sequestrant cholestyramine and the enzyme inducer rifampicin are effective. Furthermore, bezafibrate, the μ‑opioid receptor antagonists and, in Japan, nalfurafine may be used to ameliorate cholestatic pruritus. So far, no randomized controlled trials have been performed for chronic itch in other internal disorders. Antipruritic treatment is symptom-based with a focus on the effective therapy of the underlying disease.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Antipruritics; Cholestasis; Itching; Lymphoma; Renal insufficiency; chronic

Pruritus in cholestasis: facts and fiction - Beuers, Ulrich; Kremer, Andreas; Bolier, Ruth; Elferink, Ronald P. J. Oude (Hepatology, 2014)
Pruritus is a common symptom in patients with cholestatic liver diseases such as primary biliary cirrhosis, primary sclerosing cholangitis, intrahepatic cholestasis of pregnancy, or hereditary pediatric cholestatic disorders and may accompany, although less frequently, many other liver diseases. Recent findings indicate that lysophosphatidic acid (LPA), a potent neuronal activator, and autotaxin (ATX; ectonucleotide pyrophosphatase/phosphodiesterase 2), the enzyme which forms LPA, may form a key element of the long-sought pruritogenic signaling cascade in cholestatic patients suffering from itch. Serum ATX, but no other pruritogen candidate studied so far, correlates with pruritus intensity and responds to therapeutic interventions. In this comprehensive review, we provide a short update on actual insights in signal transmission related to pruritus and discuss pruritogen candidates in cholestasis. We also summarize evidence-based and guideline-approved as well as experimental therapeutic approaches for patients suffering from pruritus in cholestasis.
EVALuna2:1864

Pruritus in Psoriasis - Correlation to the Severity of the clinical appearance of the Skin? - Achterberg, Fritz Leonard; Kremer, Andreas; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Pruritus in systemic diseases : Common and rare etiologies - Kremer, Andreas; Mettang, T. (Hautarzt, 2016)
Chronic pruritus is a symptom of various internal disorders. In contrast to dermatological diseases, pruritus does not present with primary skin alterations in these patients. However, intense scratching may cause secondary skin changes such as abrasion, excoriation, prurigo nodularis, or in rare cases even scaring. The most common internal medicine causes for chronic pruritus are chronic kidney disease, hepatobiliary and hematological disorders as well as adverse drug reactions. Pruritus is less commonly seen in patients with endocrine or metabolic diseases, malabsorption syndromes, infectious diseases and solid tumors. The pathogenesis of pruritus in these disorders remains largely elusive, albeit preliminary insights have been gained for uremic and cholestatic pruritus. Antipruritic treatment is therefore symptomatic in most cases and may represent a clinical challenge. The calcium channel blockers gabapentin and pregabalin have the best proven efficacy in chronic kidney disease-associated pruritus. In Japan nalfurafine, a ?-opioid receptor agonist, has been licensed for this indication. UVB light may also attenuate uremic symptoms. In patients suffering from hepatobiliary disorders the sequestrant cholestyramine and the enzyme inducer rifampicin are effective. Furthermore, ?-opioid receptor antagonists and sertraline may be used to ameliorate cholestatic pruritus. So far, no randomized controlled trials have been performed for chronic itch in other internal medicine disorders. Antipruritic treatment is mainly based on effective therapy of the underlying disease.
EVALuna2:2200

Pruritus strongly reduces quality of life in PBC patients - real life data from a large national survey - Hönig, Stefanie; Herder, B.; Kautz, A.; Trautwein, C.; Kremer, Andreas (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Purple urine in a patient after recovery from a SARS-CoV-2 infection - Vetter, Marcel; Kaufmann, Matthias; Neurath, Markus; Kremer, Andreas (International Journal of Infectious Diseases, 2021)
CRIS-Team Scopus Importer:2021-04-02
Keywords: COVID-19; PUBS; Purple urine bag syndrome

Rapid response flow cytometric assay for the detection of antibody responses to SARS-CoV-2 - Lapuente, Dennis; Maier, Clara; Irrgang, Pascal; Hübner, Julian; Peter, Antonia Sophia; Hoffmann, Markus; Enßer, Armin; Ziegler, Katharina; Winkler, Thomas; Birkholz, Torsten; Kremer, Andreas; Steininger, Philipp; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
SARS-CoV-2 has emerged as a previously unknown zoonotic coronavirus that spread worldwide causing a serious pandemic. While reliable nucleic acid–based diagnostic assays were rapidly available, only a limited number of validated serological assays were available in the early phase of the pandemic. Here, we evaluated a novel flow cytometric approach to assess spike-specific antibody responses.HEK 293T cells expressing SARS-CoV-2 spike protein in its natural confirmation on the surface were used to detect specific IgG and IgM antibody responses in patient sera by flow cytometry. A soluble angiotensin-converting-enzyme 2 (ACE-2) variant was developed as external standard to quantify spike-specific antibody responses on different assay platforms. Analyses of 201 pre-COVID-19 sera proved a high assay specificity in comparison to commercially available CLIA and ELISA systems, while also revealing the highest sensitivity in specimens from PCR-confirmed SARS-CoV-2-infected patients. The external standard allowed robust quantification of antibody responses among different assay platforms. In conclusion, our newly established flow cytometric assay allows sensitive and quantitative detection of SARS-CoV-2-specific antibodies, which can be easily adopted in different laboratories and does not rely on external supply of assay kits. The flow cytometric assay also provides a blueprint for rapid development of serological tests to other emerging viral infections
CRIS-Team Scopus Importer:2020-10-30
Keywords: Antibodies; Coronavirus; Flow cytometry; SARS-CoV-2; Serology

Rare frameshift mutation in SERPINA3 contributes to generalized pustular psoriasis - Hüffmeier, Ulrike; Sticht, Heinrich; Wenzel, J.; Wilsmann-Theis, D.; Wolff, K.; Löhr, Sabine; Frey, Benjamin; Hahn, M.; Ekici, Arif Bülent; Uebe, S.; Thiel, Christian; Wiesmann da Silva Reis, André; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Rare Loss-of-Function Mutation in SERPINA3 in Generalized Pustular Psoriasis - Frey, Silke; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Gerschütz, Anne; Wolf, Katharina; Löhr, Sabine; Haskamp, Stefan; Frey, Benjamin; Hahn, Madelaine; Ekici, Arif Bülent; Uebe, Steffen; Thiel, Christian; et al. (Journal of Investigative Dermatology, 2020)
CRIS-Team Scopus Importer:2020-03-06

Reply: To PMID 24807046 - Elferink, Ronald Oude; Bolier, Ruth; Kremer, Andreas; Beuers, Ulrich (Hepatology, 2015)
EVALuna2:2021

Retrograde inspection vs standard forward view for the detection of colorectal adenomas during colonoscopy: A back-to-back randomized clinical trial - Rath, Timo; Pfeifer, Lukas; Neufert, Clemens; Kremer, Andreas; Leppkes, Moritz; Hoffman, Arthur; Neurath, Markus; Zopf, Steffen (World Journal of Gastroenterology, 2020)
BACKGROUND: The adenoma detection rate (ADR) is inversely associated with the incidence of interval colorectal cancer and serves as a benchmark quality criterion during screening colonoscopy. However, adenoma miss rates reach up to 26% and studies have shown that a second inspection of the right colon in retroflected view (RFV) can increase ADR. AIM: To assess whether inspection of the whole colon in RFV compared to standard forward view (SFV) can increase ADR. METHODS: Patients presenting for screening or surveillance colonoscopy were invited to participate in this randomized controlled trial and randomized into two arms. In RFV arm colonoscopy was initially performed with SFV, followed by a second inspection of the whole colon in RFV. In the SFV arm first withdrawal was performed with SFV, followed by a second inspection of the whole colon again with SFV. Number, size and morphology of polyps found during first and second inspection in each colonic segment were recorded and all polyps were removed and sent for histopathology in separate containers. RESULTS: Two hundred and five patients were randomly assigned to the RFV (n = 101) and SFV (n = 104) arm. In the RFV arm, both polyp detection rate (PDR) and ADR were increased under second inspection in RFV (PDR 1st SFV: 39.8%, PDR 2nd RFV: 46.6%; ADR 1st SFV: 35.2%, ADR 2nd RFV: 42%). Likewise, in the SFV arm, PDR and ADR were increased under second inspection (PDR 1st SFV: 37.5%, PDR 2nd SFV: 46.6%; ADR 1st SFV: 34.1%, ADR 2nd SFV: 44.3%) with no significant differences in ADR and PDR between the SFV and RFV arm. Mean number of adenomas per patient (APP) was increased in the RFV and SFV (APP RFV arm: 1st SFV: 1.71; 2nd RFV: 2.38; APP SFV arm: 1st SFV: 1.83, 2nd SFV:2.2). The majority of adenomas additionally found during second inspection in RFV or in SFV were located in the transverse and left-sided colon and were > 5 mm in size. CONCLUSION: Second inspection of the whole colon leads to increased adenoma detection with no differences between SFV and RFV. Hence, increased detection is most likely a feature of the second inspection itself but not of the inspection mode.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Adenoma; Adenoma detection rate; Colonoscopy; Colorectal cancer

S2k guideline: Diagnosis and treatment of chronic pruritus - Ständer, Sonja; Zeidler, Claudia; Augustin, Matthias; Darsow, Ulf; Kremer, Andreas; Legat, Franz J.; Koschmieder, Steffen; Kupfer, Jörg; Mettang, Thomas; Metz, Martin; Nast, Alexander; Raap, Ulrike; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Pruritus is a cross-disciplinary leading symptom of numerous diseases and represents an interdisciplinary diagnostic and therapeutic challenge. In contrast to acute pruritus, chronic pruritus (CP) is a symptom of various diseases that is usually difficult to treat. Scratching and the development of scratch-associated skin lesions can alter the original skin status. In the presence of an itch-scratch-cycle, even secondary diseases such as chronic prurigo can develop. Chronic pruritus leads to considerable subjective suffering of those affected, which can result in restrictions on the health-related quality of life such as sleep disturbances, anxiety, depressiveness, experience of stigmatization and/or social withdrawal up to clinically relevant psychic comorbidities. Medical care of patients should therefore include (a) interdisciplinary diagnosis and therapy of the triggering underlying disease, (b) therapy of the secondary symptoms of pruritus (dermatological therapy, sleep promotion, in the case of an accompanying or underlying psychological or psychosomatic disease an appropriate psychological-psychotherapeutic treatment) and (c) symptomatic antipruritic therapy. The aim of this interdisciplinary guideline is to define and standardize the therapeutic procedure as well as the interdisciplinary diagnosis of CP. This is the short version of the updated S2k-guideline for chronic pruritus. The long version can be found at www.awmf.org.
CRIS-Team Scopus Importer:2022-10-28

S2k Guidelines for the diagnosis and treatment of chronic pruritus - update - short version - Staender, Sonja; Zeidler, Claudia; Augustin, Matthias; Bayer, Gudrun; Kremer, Andreas; Legat, Franz J.; Maisel, Peter; Mettang, Thomas; Metz, Martin; Nast, Alexander; Niemeier, Volker; Raap, Ulrike; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Associated with a host of different diseases, pruritus is a cardinal symptom that poses an interdisciplinary diagnostic and therapeutic challenge. Over time, that symptom may progress independently of the initial cause, thus losing its function as a warning sign and turning into a clinically relevant disease of its own. In Germany, approximately 13.5 % of the general population are affected by chronic pruritus, with an incidence of 7 %. All forms of chronic pruritus require targeted treatment consisting of (a) diagnosis and management of the underlying disease, (b) dermatological treatment of primary or secondary (for example, dry skin, scratch lesions) symptoms, (c) symptomatic antipruritic treatment, and (d) psychological/psychotherapeutic treatment in case of an underlying or associated psychological or psychosomatic condition. Medical care of patients with chronic pruritus should therefore include an interdisciplinary approach, in particular with respect to diagnosis and therapy of the underlying disease as well as in terms of the management of treatment and adverse events. The objective of the present interdisciplinary guidelines is to define and standardize diagnostic and therapeutic procedures in patients with chronic pruritus. This is a short version of the current S2 guidelines on chronic pruritus. The long version may be found at www.awmf.org.
EVALuna2:33898

S2k Leitlinie: Diagnostik und Therapie des chronischen Pruritus - Ständer, Sonja; Zeidler, Claudia; Augustin, Matthias; Darsow, Ulf; Kremer, Andreas; Legat, Franz J.; Koschmieder, Steffen; Kupfer, Jörg; Mettang, Thomas; Metz, Martin; Nast, Alexander; Raap, Ulrike; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-10-28

Seladelpar (MBX-8025), a selective PPAR-δ agonist, in patients with primary biliary cholangitis with an inadequate response to ursodeoxycholic acid: a double-blind, randomised, placebo-controlled, phase 2, proof-of-concept study - Jones, David; Boudes, Pol F.; Swain, Mark G.; Bowlus, Christopher L.; Galambos, Michael R.; Bacon, Bruce R.; Doerffel, Yvonne; Gitlin, Norman; Gordon, Stuart C.; Odin, Joseph A.; Sheridan, David; Woerns, Markus-Alexander; et al. (Lancet Gastroenterology and Hepatology, 2017)
BACKGROUND: Many patients with primary biliary cholangitis have an inadequate response to first-line therapy with ursodeoxycholic acid. Seladelpar is a potent, selective agonist for the peroxisome proliferator-activated receptor-delta (PPAR-δ), which is implicated in bile acid homoeostasis. This first-in-class study evaluated the anti-cholestatic effects and safety of seladelpar in patients with an inadequate response to ursodeoxycholic acid. METHODS: The study was a 12-week, double-blind, placebo-controlled, phase 2 trial of patients with alkaline phosphatase of at least 1·67 times the upper limit of normal (ULN) despite treatment with ursodeoxycholic acid. Patients, recruited at 29 sites in North America and Europe, were randomly assigned to placebo, seladelpar 50 mg/day, or seladelpar 200 mg/day while ursodeoxycholic acid was continued. Randomisation was done centrally (1:1:1) by a computerised system using an interactive voice-web response system with a block size of three. Randomisation was stratified by region (North America and Europe). The primary outcome was the percentage change from baseline in alkaline phosphatase over 12 weeks, analysed in the modified intention-to-treat (ITT) population (any randomised patient who received at least one dose of medication and had at least one post-baseline alkaline phosphatase evaluation). This study is registered with ClinicalTrials.gov (NCT02609048) and the EU Clinical Trials Registry (EudraCT2015-002698-39). FINDINGS: Between Nov 4, 2015, and May 26, 2016, 70 patients were screened at 29 sites in North America and Europe. During recruitment, three patients treated with seladelpar developed fully reversible, asymptomatic grade 3 alanine aminotransferase increases (one on 50 mg, two on 200 mg), ranging from just over five to 20 times the ULN; as a result, the study was terminated after 41 patients were randomly assigned. The modified ITT population consisted of 12 patients in the placebo group, 13 in the seladelpar 50 mg group, and 10 in the seladelpar 200 mg group. Mean changes from baseline in alkaline phosphatase were -2% (SD 16) in the placebo group, -53% (14) in the seladelpar 50 mg group, and -63% (8) in the seladelpar 200 mg group. Changes in both seladelpar groups versus placebo were significant (p<0·0001 for both groups vs placebo), with no significant difference between the two seladelpar groups (p=0·1729). All five patients who received seladelpar for 12 weeks had normal alkaline phosphatase values at the end of treatment, based on a central laboratory ULN for alkaline phosphatase of 116 U/L. The most frequently reported adverse events were pruritus (16%; one patient on placebo, four on seladelpar 50 mg, and one on seladelpar 200 mg), nausea (13%; one patient on placebo, three on seladelpar 50 mg, and one on seladelpar 200 mg), diarrhoea (10%; two patients on placebo, one on seladelpar 50 mg, and one on seladelpar 200 mg), dyspepsia (8%; two patients on seladelpar 50 mg and one on seladelpar 200 mg), muscle spasms (8%; three patients on seladelpar 200 mg), myalgia (8%; one patient on placebo and two on seladelpar 200 mg), and dizziness (8%; one patient on placebo and two on seladelpar 50 mg). INTERPRETATION: Seladelpar normalised alkaline phosphatase levels in patients who completed 12 weeks of treatment. However, treatment was associated with grade 3 increases in aminotransferases and the study was stopped early. The effects of seladelpar should be explored at lower doses. FUNDING: CymaBay Therapeutics.
EVALuna2:35253

Serum Autotaxin Activity Correlates With Pruritus in Pediatric Cholestatic Disorders - Kremer, Andreas; Gonzales, Emmanuel; Schaap, Frank G.; Elferink, Ronald P. J. Oude; Jacquemin, Emmanuel; Beuers, Ulrich (Journal of Pediatric Gastroenterology and Nutrition, 2016)
Pruritus is a common symptom of cholestatic liver disorders. The present study aimed at evaluating autotaxin (ATX), a lysophospholipase recently identified as potential cause for cholestatic pruritus, in pediatric cholestatic diseases presenting with or without itching.A cohort of 45 children consisting of 14 patients experiencing itching (Alagille syndrome [n = 10], complete extrahepatic biliary atresia [n = 2], neonatal sclerosing cholangitis (n = 1), progressive familial intrahepatic cholestasis type 2 [n = 1]), 9 patients with bile acid synthesis defects (3?-hydroxy-C27-steroid-oxidoreductase [n = 7] and ?-3-oxosteroid-5?-reductase deficiency [n = 2]), and 22 healthy children were studied. Serum ATX activity and total serum bile salt were determined enzymatically, ATX protein content was semiquantified by Western blotting. Using real-time polymerase chain reaction, ATX mRNA expression was studied in HepG2 cells treated with farnesoid-X-receptor agonists or vehicle.Serum ATX activity was increased in pruritic children with Alagille and other cholestatic syndromes (mean ± standard deviation: 16.1 ± 4.3 nmol · mL · min) compared with children with nonpruritic cholestatic diseases with bile acid synthesis defects (10.4 ± 4.7 nmol · mL · min; P < 0.01) and healthy controls (7.6 ± 2.3 nmol · mL · min; P < 0.001). ATX protein levels closely correlated with serum ATX activity. Serum ATX activity and total serum bile salt showed a linear correlation with itch intensity (r = 0.66, P < 0.001 and r = 0.80, P < 0.001, respectively). No correlation was observed between ATX activity and bilirubin. ATX mRNA expression in HepG2 cells was not induced by farnesoid-X-receptor ligands.Serum ATX activity correlated with itch intensity in children with cholestatic diseases. Bile salts did not increase ATX expression in vitro. ATX inhibitors may be useful antipruritic agents in pediatric cholestatic disorders.
EVALuna2:2105

Serum Autotaxin is a Marker of the Severity of Liver Injury and Overall Survival in Patients with Cholestatic Liver Diseases - Wunsch, Ewa; Krawczyk, Marcin; Milkiewicz, Malgorzata; Trottier, Jocelyn; Barbier, Olivier; Neurath, Markus; Lammert, Frank; Kremer, Andreas; Milkiewicz, Piotr (Scientific Reports, 2016)
Autotaxin (ATX) is involved in the synthesis of lysophosphatidic acid. Both have recently been linked to cholestatic pruritus and liver injury. We aimed to investigate whether ATX is an indicator of cholestatic liver injury, health-related quality of life (HRQoL) and prognosis based on a group of 233 patients, 118 with primary biliary cholangitis (PBC) and 115 with primary sclerosing cholangitis (PSC). Patients were followed for 1-60 months, cumulative survival rates were calculated. ATX activity was significantly higher in both groups than in the 103 controls, particularly in patients with cirrhosis and in patients with longer disease duration. Ursodeoxycholic acid (UDCA) non-responders with PBC exhibited increased ATX activity. ATX activity was correlated with liver biochemistry, MELD, Mayo Risk scores and was associated with worse disease-specific HRQoL aspects. In both groups, Cox model analysis indicated that ATX was a negative predictor of survival. Increased ATX levels were associated with a 4-fold higher risk of death/liver transplantation in patients with PBC and a 2.6-fold higher risk in patients with PSC. We conclude that in patients with cholestatic conditions, ATX is not only associated with pruritus but also indicates impairment of other HRQoL aspects, liver dysfunction, and can serve as a predictor of survival.
EVALuna2:2194

Serum IP-10 levels and increased DPPIV activity are linked to circulating CXCR3+ T cells in cholestatic HCV patients - Rau, Monika; Schmitt, Johannes; Berg, Thomas; Kremer, Andreas; Stieger, Bruno; Spanaus, Katharina; Bengsch, Bertram; Romero, Marta R.; Marin, Jose J.; Keitel, Verena; Klinker, Hartwig; Tony, Hans-Peter; et al. (PLoS ONE, 2018)
BACKGROUND & AIMS: Serum interferon-gamma-inducible protein-10 (IP-10) is elevated in cholestatic liver diseases and predicts response to antiviral therapy in patients with chronic hepatitis C virus (HCV) infection. Dipeptidylpeptidase 4 (DPPIV) cleaves active IP-10 into an inactive form, which inhibits recruitment of CXCR3+ T cells to the liver. In this study the link between IP-10 levels, DPPIV activity in serum and CXCR3+ T cells is analysed in cholestatic and non-cholestatic liver patients. METHODS: In serum DPPIV activity (by enzymatic assay), IP-10 (by ELISA) and bile acids (BA) (by enzymatic assay) were analysed in 229 naive HCV genotype (GT) 1 patients and in 16 patients with cholestatic liver disease. In a prospective follow-up (FU) cohort of 27 HCV GT 1 patients peripheral CD3+CXCR3+, CD4+CXCR3+ and CD8+CXCR3+ cells were measured by FACS. RESULTS: In 229 HCV patients serum IP-10 levels correlated positively to DPPIV serum activity. Higher IP-10 levels and DPPIV activity were detected in cholestatic and in cirrhotic HCV patients. Increased IP-10 serum levels were associated with therapeutic non-response to antiviral treatment with pegylated-interferon and ribavirin. In the HCV FU cohort elevated IP-10 serum levels and increased BA were associated with higher frequencies of peripheral CD3+CXCR3+, CD4+CXCR3+ and CD8+CXCR3+ T cells. Positive correlation between serum IP-10 levels and DPPIV activity was likewise validated in patients with cholestatic liver diseases. CONCLUSIONS: A strong correlation between elevated serum levels of IP-10 and DPPIV activity was seen in different cholestatic patient groups. Furthermore, in cholestatic HCV patients a functional link to increased numbers of peripheral CXCR3+ immune cells could be observed. The source of DPPIV release in cholestatic patients remains open.
EVALuna2:35126

Severity of COVID-19 disease is related to hyperactivation and altered migratory capacity of T cells - Spörl, Silvia; Kremer, Anna-Lena; Aigner, Michael; Eisenhauer, Nina; Koch, P.; Meretuk, L.; Loeffler, P.; Lutzny-Geier, Gloria; Vetter, Marcel; Bruns, Heiko; Mackensen, Andreas; Kremer, Andreas; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Subnanomolar MAS-related G protein-coupled receptor-X2/B2 antagonists with efficacy in human mast cells and disease models - Al Hamwi, Ghazl; Alnouri, Mohamad Wessam; Verdonck, Sven; Leonczak, Piotr; Chaki, Shaswati; Frischbutter, Stefan; Kolkhir, Pavel; Matthey, Michaela; Kopp, Constantin; Bednarski, Marek; Riedel, Yvonne K.; Marx, Daniel; et al. (Signal Transduction and Targeted Therapy, 2025)
The MAS-related G protein-coupled receptor-X2 (MRGPRX2), an orphan receptor expressed on mast cells (MCs), is upregulated upon inflammation and induces hypersensitivity and inflammatory diseases. In contrast to the large number of MRGPRX2 agonists, only a few antagonists have been described, and no optimization has been reported to improve potency, selectivity, and drug-like properties. Antagonists with ancillary inhibition of the putative mouse ortholog MRGPRB2 have not been described. Here, we present a multi-disciplinary approach involving chemistry, biology, and computational science, resulting in the development of a small-molecule MRGPRX2 antagonist (PSB-172656, 3-ethyl-7,8-difluoro-2-isopropylbenzo[4,5]imidazo [1,2-a] pyrimidin-4(1H)-one) based on a fragment screening hit. The compound exhibits metabolic stability, low cytotoxicity, and competitive blockade of MRGPRX2 activation induced by a diverse range of agonists. It displays subnanomolar potency in Ca2+ mobilization assays (Ki value 0.142 nM) and was found to block MRGPRX2-mediated Gαq and Gαi1 dissociation, in addition to β-arrestin-2 recruitment. PSB-172656 is selective for MRGPRX2 versus all other MRGPRX subtypes. Its effect on MCs was confirmed in cell lines, including rat basophilic leukemia cells (RBL-2H3) recombinantly expressing human MRGPRX2, human Laboratory of Allergic Diseases 2 (LAD2) MCs, and native human skin MCs. PSB-172656 was found to additionally block the putative mouse ortholog of MRGPRX2, MRGPRB2, as determined in Ca2+ mobilization assays (Ki 0.302 nM), and to prevent mouse tracheal contractions, local allergic reactions, and systemic anaphylactic symptoms. PSB-172656 constitutes a unique pharmacological tool and has the potential to be developed as a drug for mast cell-mediated hypersensitivity reactions and chronic inflammatory diseases, addressing a huge unmet medical need.
CRIS-Team Scopus Importer:2025-05-02

Sub-optimale Behandlung von Patienten mit Primär Biliärer Cholangitis (PBC) im klinischen Alltag der deutschen PBC Kohorte Sub-optimal therapy of patients with primary biliary cholangitis (PBC) in the real-life stetting of the German PBC cohort - Wiegand, Johannes; Franke, Annegret; Müller, Tobias; Stein, Kerstin; Bantel, Heike; Günther, Rainer; Denk, Gerald; Reuken, Philipp A.; Schattenberg, Jörn M.; Naumann, Uwe; Böttler, Tobias; Weber, Andreas; et al. (Zeitschrift für Gastroenterologie, 2024)
Real-world data on the management of patients with primary biliary cholangitis (PBC) are so far scarce in Germany. Therefore, we aimed to establish a nationwide registry and describe the clinical characteristics and therapy of PBC patients.Three different cohorts defined as ursodeoxycholic acid (UDCA) responders, as inadequate responders according to Paris II criteria, and as newly diagnosed patients were prospectively recruited.This manuscript includes the baseline data of the project.In total, 33/77 (43%) contacted centres (58% of university hospitals, 38% of non-university hospitals, and 24% of private practices) recruited 515 patients including 204 UDCA responders, 221 inadequate responders to UDCA, and 90 newly diagnosed patients.All patients were treated with UDCA; however, a UDCA dosage below the recommended dosage of 13 mg/kg/d was observed in 38.5% of individuals after 12 months of treatment. UDCA dosages were lower in nonacademic compared to academic centres.Only 75/219 (38.5%) of inadequate responders to UDCA received a second-line therapy with obeticholic acid (OCA) and/or bezafibrate (BZF). OCA (13% vs. 4.5%) and BZF (14% vs. 6.5%) were significantly more often prescribed by academic vs. nonacademic centres.Pruritus (27% vs. 15.5%), fatigue (23% vs. 4.5%), and sicca syndrome (14% vs. 1%) were significantly more often reported by academic centres.The German PBC registry could be established, which indicates suboptimal therapy in a relevant proportion of patients and shows significant differences between academic and nonacademic centres. Results are fundamental to improving clinical management at different levels of care.
CRIS-Team Scopus Importer:2024-11-22

Successful Multidisciplinary Treatment with Secondary Metastatic Liver Resection after Downsizing by Palliative Second-Line Treatment of Colorectal Cancer: A Curative Option - Wein, Axel; Görtz, Rüdiger; Wolff, Kerstin; Ostermeier, Nicola; Busse, Daniel; Kremer, Andreas; Koch, Franz; Hagel, Alexander; Farnbacher, Michael; Kammerer, Ferdinand J.; Neurath, Markus; Grützmann, Robert; et al. (Case Reports in Oncology, 2016)
The prognostic outcome following progression after palliative first-line treatment for patients suffering from metastatic colorectal adenocarcinoma is generally poor. Long-term relapse-free survival with palliative second-line treatment may be achieved in only a limited number of individual cases.A 37-year-old patient presented with bilobar liver metastases of colon cancer confirmed by histology with wild-type K-RAS (exon 2). Due to progressive disease after eight cycles of first-line therapy with FOLFIRI plus cetuximab, second-line chemotherapy with modified FOLFOX4 (mFOLFOX4) plus bevacizumab was initiated. During four cycles of mFOLFOX4 plus bevacizumab (2 months), no higher-grade toxicity occurred. Liver MRI with contrast medium revealed downsizing of the segment II/III metastases, as well as regressive, small, faint, hardly definable lesions in segments VI and IVb. The interdisciplinary tumor board of the University of Erlangen thus decided to perform resection of the liver metastases. Segments II and III were resected, and the liver metastases in segments IVa and VI were excised (R0). Histopathology confirmed three of the R0-resected metastases to be completely necrotic, with residual scarring. As perioperative therapy, four additional cycles of mFOLFOX4 plus bevacizumab were administered postoperatively. No higher-grade toxicity was observed. Three years after the initial diagnosis, the patient is relapse free, professionally fully reintegrated, and has an excellent performance status.Patients suffering from metastatic colorectal cancer may benefit from multidisciplinary treatment with secondary metastatic liver resection after downsizing by palliative second-line treatment. In individual cases, patients may even have a curative treatment option, provided that close interdisciplinary collaboration exists.
EVALuna2:2220

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Teufelskreis aus Jucken und Kratzen - Kremer, Andreas (Pharmazeutische Zeitung, 2019)
CRIS-Team Scopus Importer:2019-11-12

THE AMOUNT OF LIVER TISSUE IS ESSENTIAL FOR ACCURATE HISTOLOGICAL STAGING IN PATIENTS WITH AUTOIMMUNE HEPATITIS - Vetter, Marcel; Kremer, Andreas; Agaimy, Abbas; Konturek, P. C.; Pfeifer, L.; Neurath, Markus; Zopf, Steffen; Siebler, Jürgen (Journal of Physiology and Pharmacology, 2021)
The gold standard for the evaluation of liver fibrosis is histology. However, the heterogenous distribution of fibrosis limits the sensitivity of histology. The collection of two samples with a 16G needle is therefore recommended to reduce the risk of sampling error. The aim of this study was to investigate whether this standard is also applicable to patients with autoimmune hepatitis (AIH). This retrospective study included patients with AIH, who underwent mini-laparoscopic biopsy at our center between 2011 and 2020 (n = 32). Diagnosis was verified by usage of the simplified AIH score (>= 6). Patients were categorized into three groups, based on the number of portal fields (PF) in the collected liver tissue (< 10 PF, 10 - 19 PF, >= 20 PF). We correlated the histological staging for these groups with the mini-laparoscopic fibrosis score (MLFS). Furthermore, non-invasive methods for the assessment of fibrosis were correlated with the histological staging (acoustic radiation force impulse (ARFI) and FIB-4 score). MLFS correlated well with histological staging (r = 0.649, p = 0.0001). The correlation between MLFS and histology improved with higher numbers of histologically analyzed portal fields (< 10 PF: r = 0.400, p = 0.378; 10 - 19 PF: r = 0.5467, p = 0.023; >= 20 PF: r = 0.956, p = 0.0002). The probability of collecting at least 10 or 20 portal fields was dependent on the number and diameter of the samples. For all patients with at least two 16G biopsies, 10 or more PF were available. With three 16G biopsies, at least 20 PF were obtained for all patients. ARFI correlated with MLFS and histological staging only in patients with low/moderate-grade inflammation as defined by ALT < 10xULN (upper limit of normal) (MLFS: r = 0.723; p = 0.004; histology: r = 0.619, p = 0.018). FIB-4 did not correlate with histological staging. The amount of liver tissue obtained by liver biopsy is crucial to minimalize the risk of sampling error and thus underestimation of fibrosis. This study was the first to investigate the amount of liver tissue required for histological staging in AIH. Our data suggest that diagnostic accuracy is likely to be higher with 20 PF compared to the generally recommended 10 PF. We therefore recommend to perform three biopsies with a 16G needle in (suspected) AIH patients. ARFI correlated well with histological staging unless inflammatory activity is high.
CRIS-Team WoS Importer:2021-10-29

The G protein-coupled receptor MRGX4 is a novel receptor for bile salts expressed on sensory neurons - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (SWISS MEDICAL WEEKLY, 2021)
CRIS-Team WoS Importer:2022-03-11

THE NOX1/4 INHIBITOR GKT831 ACHIEVES CLINICALLY MEANINGFUL REDUCTIONS IN LIVER STIFFNESS, ATTENUATES CHOLESTASIS, AND IMPROVES QUALITY OF LIFE IN PATIENTS WITH PRIMARY BILIARY CHOLANGITIS - Huang, Jonathan C.; Invernizzi, Pietro; Dalekos, George N.; Nevens, Frederik; Van Vlierberghe, Hans; Zigmond, Ehud; Andrade, Raul J.; Ben-Ari, Ziv; Heneghan, Michael A.; Harrison, Stephen A.; Minuk, Gerald Y.; Schattenberg, Joern; et al. (HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-25

Therapy adaption by dose titration of obeticholic acid in a 57-year-old female patient with PBC and advanced liver fibrosis - Vetter, Marcel; Dietrich, Peter; Kremer, Andreas (SWISS MEDICAL WEEKLY, 2021)
CRIS-Team WoS Importer:2022-03-11

The safety and efficacy of nasobiliary drainage in the treatment of refractory cholestatic pruritus: a multicentre European study - Hegade, V. S.; Krawczyk, M.; Kremer, Andreas; Kuczka, Judith; Gaouar, F.; Kuiper, E. M. M.; Van Buuren, H. R.; Lammert, F.; Corpechot, C.; Jones, D. E. J. (Alimentary Pharmacology & Therapeutics, 2016)
Pruritus is a common symptom associated with cholestatic liver diseases. To date only small single centre case series have suggested efficacy of nasobiliary drainage in relieving cholestatic pruritus.To perform a multicentre study to evaluate the safety and efficacy of nasobiliary drainage in cholestatic pruritus.This was a retrospective study of all patients treated with nasobiliary drainage for refractory cholestatic pruritus between 2006 and 2015 at five European centres. Pruritus was quantified using a visual analogue scale (VAS) and liver enzymes, serum bilirubin and total serum bile salts (TBS) were measured before (pre-NBD) and after nasobiliary drainage (post-NBD). We analysed the duration of treatment response and associated complications.In total, 27 patients (59% females) underwent 29 nasobiliary drainage procedures. The median duration of NBD was 7 days. NBD decreased pruritus in 89.6% of cases (VAS from 10.0 to 0.3, P < 0.0001). The median percentage decline in pruritus VAS was 94% and 33% of patients were free of pruritus within 24 h of starting drainage. The duration of treatment response was independent of duration of drainage (P = 0.12) and bile output. Significant improvements were seen in the median levels of serum alkaline phosphatase (P = 0.001) and serum bilirubin (P = 0.03) but not in serum TBS (P = 0.07). Mild post-endoscopic retrograde cholangiopancreatography pancreatitis (31%) was the most frequent complication.Nasobiliary drainage is effective in relieving cholestatic pruritus in most patients and has favourable effect on biomarkers of cholestasis. Nasobiliary drainage may be associated with high risk of adverse events, especially pancreatitis. Prospective studies are needed to confirm our findings.
EVALuna2:2039

Three years of obeticholic Acid (OCA) therapy results in histological improvements in patients with primary biliary cholangitis: further analysis of the POISE Biopsy substudy - Bowlus, C. L.; Pockros, P. J.; Kremer, Andreas; Pares, A.; Forman, L. M.; Drenth, J. P. H.; Ryder, S.; Terracciano, L.; Floreani, A.; Jin, Y.; Lieberman, A.; Pencek, R.; et al. (DIGESTIVE AND LIVER DISEASE, 2019)
CRIS-Team WoS Importer:2019-03-01

Total bile acids in the maternal and fetal compartment in relation to placental ABCG2 expression in preeclamptic pregnancies complicated by HELLP syndrome - Jebbink, Jiska; Veenboer, Geertruda; Boussata, Souad; Keijser, Remco; Kremer, Andreas; Elferink, Ronald Oude; Van Der Post, Joris; Afink, Gijs; Ris-Stalpers, Carrie (BBA - Biochimica et Biophysica Acta, 2015)
To investigate total bile acid (TBA) levels in maternal (MB) and umbilical cord blood (UCB) in normotensive, preeclamptic (PE), and PE pregnancies complicated by hemolysis elevated liver enzymes and low platelets (HELLP) syndrome in the context of ABCG2 placental gene expression levels, a recently reported placental bile acid transporter.TBA levels were determined in 83 paired MB and UCB samples of normotensive, PE and PE/HELLP pregnancies and in 22 paired arterial and venous UCB samples from uncomplicated term pregnancies. ABCG2 gene expression was measured in 104 human placentas by reverse transcriptase quantitative polymerase chain reaction.Overall, TBA levels in MB are higher compared to levels in UCB (p<0.0001), but this comparison looses statistical significance for the 11 PE/HELLP cases. TBA levels in maternal blood are increased in PE/HELLP compared to PE pregnancies (p=0.016). TBA levels in arterial and venous UCB from 22 normotensive pregnancies are not statistically different. ABCG2 expression is reduced in pregnancies where preeclampsia is further complicated by HELLP syndrome. ABCG2 expression in human placenta is not correlated with TBA levels in either the maternal or fetal compartment.Increased maternal TBA levels in PE/HELLP pregnancies indicate a relation between bile acids in the maternal circulation and HELLP syndrome. As overall TBA levels in maternal blood are increased compared to UCB, we conclude that the placenta partly protects the fetus from increased maternal TBA levels. This consistent difference in TBA levels between the maternal and fetal compartment is unrelated to the placental expression of ABCG2.
EVALuna2:1976

Treatment efficacyand safety of seladelpar, a selective peroxisome proliferator-activated receptor delta agonist, in primary biliary cholangitis patients: 12-and 26-week analysis from an ongoing international, randomized, dose raging phase 2 study - Hirschfield, G.; Boudes, P.; Bowlus, C.; Gitlin, N.; Michael, G.; Harrison, S.; Gordon, S. C.; Aspinall, R.; Doerffel, Y.; Kremer, Andreas; Sheridan, D.; Bacon, B.; et al. (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

Treatment of chronic itch in systemic disease : Current standards - Mettang, T.; Staender, S.; Kremer, Andreas (Internist, 2015)
Chronic itch (CI) is a frequent and sometimes tormenting symptom in many skin and systemic diseases. In systemic diseases, it mostly appears on primarily unaffected skin. As a sequelae of intense scratching, secondary skin lesions such as excoriations, scars, and prurigo nodularis may occur. Due to the lack of valid pathogenetic concepts and good clinical trials, the therapy of CI remains mostly symptomatic. In Europe almost all drugs used to treat CI are not approved for this indication. CI is frequent in patients with chronic kidney diseases in advanced stages. Gabapentin and pregabalin, anticonvulsants, and centrally acting calcium channel blockers have been shown to exert a profound effect in CI. Furthermore, UVB phototherapy has been proven to attenuate pruritus in uremic patients. Randomized controlled studies have recently shown that nalfurafine, a ?-opioid receptor agonist, is able to ameliorate itch in patients with uremic itch. In patients suffering from cholestatic itch, the anion exchange resin colestyramine and rifampicin are effective antipruritic drugs. Furthermore, µ-opioid receptor antagonists and sertraline may be used to alleviate CI in hepatic diseases. In refractory cases, naso-biliary drainage or albumin dialysis are effective invasive procedures. For the treatment of chronic itch in hematological diseases no controlled trials have been performed so far. The mainstay in these cases is to treat the underlying disease.
EVALuna2:1848

Treatment of Pruritus Secondary to Liver Disease - Düll, Miriam; Kremer, Andreas (Current Gastroenterology Reports, 2019)
Purpose of Review: Pruritus is a common extrahepatic symptom in various liver disorders, in particularly those with cholestatic features. This review summarizes epidemiology, pathophysiology, evidence-based therapeutic recommendations and currently investigated drugs for pruritus in hepatobiliary disorders. Recent Findings: Recent epidemiological data suggest pruritus as a common and relevant symptom in immune-mediated liver diseases, i.e., primary biliary cholangitis (PBC) with over 70% affected patients, up to 56% suffering from chronic pruritus. The better pathophysiological understanding of hepatic pruritus has led to the identification of novel therapeutic targets, addressed in drug trials using KOR agonists, PPAR agonists, and ileal bile acid transporter inhibitors. Summary: Hepatic itch remains among the most agonizing symptoms for affected patients and a clinical challenge for physicians. Therapeutic recommendations include a guideline-based stepwise approach starting with cholestyramine, followed by rifampicin, naltrexone, and sertraline. Bezafibrate and ileal bile acid transporter inhibitors represent promising future anti-pruritic treatment options.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Autotaxin; Bile salt; Cholestasis; Liver; Lysophosphatidic acid; Pruritus

Upregulation of CCR4 in activated CD8(+) T cells indicates enhanced lung homing in patients with severe acute SARS-CoV-2 infection - Spoerl, Silvia; Kremer, Anita; Aigner, Michael; Eisenhauer, Nina; Koch, Pauline; Meretuk, Lina; Loeffler, Patrick; Tenbusch, Matthias; Maier, Clara; Überla, Klaus; Heinzerling, Lucie; Frey, Benjamin; et al. (European Journal of Immunology, 2021)
COVID-19 is a life-threatening disease leading to bilateral pneumonia and respiratory failure. The underlying reasons why a smaller percentage of patients present with severe pulmonary symptoms whereas the majority is only mildly affected are to date not well understood.
CRIS-Team WoS Importer:2021-05-07

Uremic pruritus - Mettang, Thomas; Kremer, Andreas (Kidney International, 2015)
Uremic pruritus or chronic kidney disease-associated pruritus (CKD-aP) remains a frequent and compromising symptom in patients with advanced or end-stage renal disease, strongly reducing the patient's quality of life. More than 40% of patients undergoing hemodialysis suffer from chronic pruritus; half of them complain about generalized pruritus. The pathogenesis of CKD-aP remains obscure. Parathormone and histamine as well as calcium and magnesium salts have been suspected as pathogenetic factors. Newer hypotheses are focusing on opioid-receptor derangements and microinflammation as possible causes of CKD-aP, although until now this could not be proven. Pruritus may be extremely difficult to control, as therapeutic options are limited. The most consequential approaches to treatment are: topical treatment with or without anti-inflammatory compounds or systemic treatment with (a) gabapentin, (b) ?-opioid receptor antagonists and ?-agonists, (c) drugs with an anti-inflammatory action, (d) phototherapy, or (e) acupuncture. A stepwise approach is suggested starting with emollients and gabapentin or phototherapy as first-line treatments. In refractory cases, more experimental options as ?-opioid-receptor-antagonists (i.e., naltrexone) or ?-opioid-receptor agonist (nalfurafine) may be chosen. In desperate cases, patients suitable for transplantation might be set on 'high urgency'-status, as successful kidney transplantation will relieve patients from CKD-aP.
EVALuna2:1996

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

What are new treatment concepts in systemic itch? - Kremer, Andreas (Experimental Dermatology, 2019)
Chronic pruritus is a relevant symptom burden in various systemic diseases. It is most commonly observed in patients with chronic kidney disease, hepatobiliary and hematological disorders as well as adverse drug reaction. Recent basic research has unravelled novel treatment targets which are currently in preclinical phases, clinical trials or have already been licensed. While mu-opioid receptor antagonists have been used since decades mainly in cholestatic pruritus, the k-opioid receptor agonist nalfurafine has been licensed in Japan for chronic kidney disease-associated pruritus (CKDaP) as well as cholestatic pruritus. Further kappa-opioid receptor agonists are currently investigated in various clinical trials including CKDaP. In recent years, the calcium channel blockers gabapentin and pregabalin have also been recognized as effective anti-pruritus therapy in several internal diseases with the best evidence in chronic kidney disease-associated pruritus. Neurokinin-1 receptor antagonists have been investigated with variable benefit in CKDaP, solid tumors and lymphoproliferative disorders such as cutaneous T-cell lymphoma, Sezary syndrome. Inhibitors of the ileal bile acid transporter (IBAT) represent a selective interruption of the enterohepatic circulation and are currently investigated in various hepatobiliary disorders associated with pruritus. The current development and testing of novel drugs in clinical trials offers hope to struggling physicians and suffering patients.
CRIS-Team WoS Importer:2019-10-01